Method for producing metal carbide, metal carbide powder, and metal carbide intermediate dispersion liquid
The complex polymerization method for producing metal carbides addresses the issues of poor fluidity and roundness in existing methods, resulting in improved mixability and uniform film formation, thereby enhancing the performance of carbide tools and coatings.
Patent Information
- Application Number
- JP2024173222
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-03
- Filing Date
- 2024-10-02
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-10-02
AI Technical Summary
Existing methods for producing metal carbides result in powders with poor fluidity and roundness, leading to poor mixability with tungsten carbide, which affects the performance of carbide cutting tools and the uniformity of films formed on base materials.
A method involving a complex polymerization process using a metal hydroxide and an alkaline compound, followed by hydrogen peroxide and organic acid addition, to produce a metal carbide precursor, which is then carbonized and powdered to enhance roundness and fluidity.
The method produces metal carbides with high roundness and fluidity, improving mixability with tungsten carbide and enabling the formation of uniform films on base materials, enhancing the performance of carbide tools and film coatings.
Smart Images

Figure 2024177328000003 
Figure 2024177328000004 
Figure 2024177328000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a metal carbide, a metal carbide powder, and a metal carbide intermediate dispersion liquid. [Background technology]
[0002] Metal carbides such as tantalum carbide and niobium carbide are widely used as additives to tungsten carbide, which is the raw material for cemented carbide cutting tools such as cutting tools, tips, cutters, drills, and dies, and good mixing performance with tungsten carbide is required for manufacturing high-quality cemented carbide cutting tools. Patent Document 1 discloses, as tantalum carbide used as an additive, a tantalum carbide powder that has little powder aggregation, is fine and uniform in size, and has a low oxygen content that is stoichiometrically sufficiently bonded to carbon.
[0003] Furthermore, when a metal carbide film is formed on the surface of a carbon or ceramic substrate, it acts as a protective film that suppresses thermal decomposition of the substrate, for example, protecting the carbon material from oxidation during heating. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-31016 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, it was thought that if the particles were extremely fine, the fluidity would be poor due to aggregation, and the mixability would also be poor. In addition, in a method for producing metal carbide in which a mixture of metal oxide and carbon black is heat-treated (calcination method) and granulated as disclosed in Patent Document 1, the roundness of the produced tantalum carbide powder and tantalum carbide-niobium composite powder is low. Furthermore, the roundness is further reduced by performing a pulverization process after granulation. In this way, metal carbides with extremely fine particles and low roundness have poor fluidity, and therefore poor mixability with raw materials for cemented carbide cutting tools such as tungsten carbide, and do not become a homogeneous cemented carbide material, and the performance of cemented carbide tools produced from such raw materials is poor.
[0006] Furthermore, when a film is formed on the surface of a substrate, if the circularity is high and the fluidity is high, a uniform film can be easily formed on the surface of the substrate.
[0007] In view of the above problems, the present invention provides a method for producing a metal carbide having high circularity and high fluidity, a metal carbide powder, and a metal carbide intermediate dispersion liquid. [Means for solving the problem]
[0008] The method for producing a metal carbide according to the present invention, which has been made to solve the above problems, is a method for producing a powder-shaped metal carbide using a complex polymerization method, and includes a complexing step of mixing a metal hydroxide and an alkaline compound to produce a first mixed liquid, adding hydrogen peroxide to the first mixed liquid to produce a second mixed liquid, and further adding an organic acid to the second mixed liquid to produce a metal carbide precursor; The method includes a carbonization step of producing a metal carbide by firing the metal carbide precursor, and a powderization step of crushing the metal carbide to form a metal carbide powder. For ease of explanation, the method for producing metal carbide of the present invention, which includes a powdering step of crushing metal carbide to form metal carbide powder, will be described below as the method for producing metal carbide powder of the present invention.
[0009] In the complexing step in the method for producing a metal carbide powder of the present invention, first, a metal hydroxide described below and an alkaline compound are mixed to produce a first mixed liquid.
[0010] The metal hydroxide is preferably a hydroxide of tantalum, niobium, titanium, tungsten, molybdenum, zirconium, etc. In particular, the metal hydroxide is preferably tantalum hydroxide or niobium hydroxide.
[0011] For example, it is preferable to adjust tantalum hydroxide to contain 1 to 100 g / L of tantalum in terms of Ta2O5 by adding water (e.g., pure water). In this case, it is preferable that the tantalum concentration is 1 g / L or more in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the tantalum concentration is 100 g / L or less in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tantalic acid compound hydrate that is easily soluble in water, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. Similarly, it is preferable to adjust niobium hydroxide to contain 1 to 100 g / L of niobium in terms of Nb2O5.
[0012] The alkaline compound is preferably one or more compounds selected from ammonia, sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, and organic nitrogen compounds. Examples of the organic nitrogen compounds include amine compounds, quaternary ammonium compounds, guanidine compounds, and azole compounds, and are preferably amine compounds or quaternary ammonium compounds, and more preferably methylamine, dimethylamine, tetramethylammonium hydroxide (TMAH), or tetraethylammonium hydroxide (TEAH). The alkaline compound may be an alkaline solution in which the alkaline compound is dissolved. As the alkaline solution, an alkaline aqueous solution, particularly an aqueous ammonia solution, is preferable.
[0013] The alkaline compound content in the first mixed solution is preferably more than 0% by mass and less than 50% by mass, and more preferably 0.01% by mass or more and 4% by mass or less. From the viewpoint of reactivity and dispersibility, it is desirable to have a high content of the alkaline compound. On the other hand, since it is a volatile component, a low content is desirable from the viewpoint of suppressing volatilization during film formation in a later process. Typically, the alkaline compound content may be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, or 10% by mass or more. On the other hand, the alkaline compound content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, or 10% by mass or less.
[0014] The alkaline compound content in the first mixed solution can be expressed by the molar ratio of alkaline compound / metal hydroxide. The molar ratio of alkaline compound / metal hydroxide is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of alkaline compound / metal hydroxide may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of alkaline compound / metal hydroxide may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0015] Here, the alkaline compound in the alkaline compound / metal hydroxide molar ratio indicates the content of the alkaline compound in the first mixed solution. When two or more types of alkaline compounds are contained, the content of the alkaline compound is the total content of these two or more types of alkaline compounds. On the other hand, the metal hydroxide in the alkaline compound / metal hydroxide molar ratio indicates the content of the metal hydroxide in terms of metal atoms in the first mixed solution. When two or more types of metal hydroxides are contained, the content of the metal hydroxide in terms of metal atoms is the total content of these two or more types of metal hydroxides in terms of metal atoms.
[0016] For example, when the mixed metal hydroxide is tantalum hydroxide, the molar ratio of alkaline compound / Ta is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of alkaline compound / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of alkaline compound / Ta may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0017] In addition, when the mixed metal hydroxide is niobium hydroxide, the molar ratio of alkaline compound / Nb is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of alkaline compound / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of alkaline compound / Nb may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0018] Furthermore, when the mixed metal hydroxide is niobium hydroxide and tantalum hydroxide, the molar ratio of the alkaline compound to niobium and tantalum: alkaline compound / (Nb+Ta) is preferably more than 0 and 100 or less, more preferably 0.001 or more and 100 or less, even more preferably 0.01 or more and 50 or less, particularly preferably 0.1 or more and 30 or less, and more particularly preferably 4 or more and 20 or less. Typically, the molar ratio of the alkaline compound / (Nb+Ta) may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of the alkaline compound / (Nb+Ta) may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0019] In addition, when the alkaline compound is ammonia, the ammonia content in the first mixed solution is preferably more than 0% by mass and less than 50% by mass, and more preferably 0.01% by mass or more and 4% by mass or less. From the viewpoint of reactivity and dispersibility, it is desirable to have a high ammonia content. On the other hand, since it is a volatile component, a low ammonia content is desirable from the viewpoint of suppressing volatilization during film formation in a later process. Typically, the ammonia content may be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, or 10% by mass or more. On the other hand, the ammonia content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, or 10% by mass or less.
[0020] The content of ammonia in the first mixed liquid can be expressed by the molar ratio of NH3 / metal hydroxide. The molar ratio of NH3 / metal hydroxide is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of NH3 / metal hydroxide may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / metal hydroxide may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0021] Regarding the content of ammonia, when the mixed metal hydroxide is tantalum hydroxide, the molar ratio of NH3 / Ta is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of NH3 / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / Ta may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0022] In addition, when the mixed metal hydroxide is niobium hydroxide, the molar ratio of NH3 / Nb is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of NH3 / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / Nb may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0023] Furthermore, when the mixed metal hydroxide is niobium hydroxide and tantalum hydroxide, the molar ratio of ammonia to niobium and tantalum: NH3 / (Nb+Ta) is preferably more than 0 and 100 or less, more preferably 0.001 or more and 100 or less, even more preferably 0.01 or more and 50 or less, particularly preferably 0.1 or more and 30 or less, and more particularly preferably 4 or more and 20 or less. Typically, the molar ratio of NH3 / (Nb+Ta) may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / (Nb+Ta) may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0024] Examples of the solvent used in the complexing step in the method for producing metal carbide powder of the present invention include water, organic solvents, and mixed solvents thereof. Examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, and the like, and may be solvents obtained by mixing these organic solvents with pure water. Examples of the alcohol solvent include alcohols having 5 or less carbon atoms (methanol, ethanol, n-propanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol), acetone, and high boiling point solvents. It is preferable that the above-mentioned solvents are compatible with water.
[0025] Examples of high boiling point solvents include polyhydric alcohol solvents and glycol solvents. Examples of polyhydric alcohol solvents include glycerin (boiling point: 290°C), 1,6-hexanediol (boiling point: 250°C), and 1,7-heptanediol (boiling point: 259°C). Examples of glycol solvents include ethylene glycol (boiling point: 197.3°C), propylene glycol (boiling point: 188.2°C), diethylene glycol (boiling point: 244.3°C), triethylene glycol (boiling point: 287.4°C), oligoethylene glycol (boiling point: 287°C to 460°C), polyethylene glycol (PEG) (boiling point: 460°C or higher), polyethylene glycol (PEG)-polypropylene glycol (PPG) copolymer (boiling point: 460°C). or higher), diethylene glycol monohexyl ether (boiling point: 260°C), polyoxyalkylene monoalkyl ether (boiling point: 260°C or higher), polyoxyethylene sorbitan monolaurate (boiling point: 321°C or higher), other anionic fluorosurfactants (boiling point: 180°C or higher), amphoteric fluorosurfactants (boiling point: 180°C or higher), nonionic fluorosurfactants (boiling point: 180°C or higher), amine oxides (boiling point: 180°C or higher), etc. The above boiling points are those at 1 atmospheric pressure.
[0026] The solvent used in the complexing step in the method for producing a metal carbide powder of the present invention may contain a resin such as a polyolefin compound or a polyvinyl compound. The resin added to the solvent may be an anionic water-soluble resin and / or a nonionic water-soluble resin.
[0027] Here, the cationic water-soluble resin is a resin that has a positive charge in the polymer in water of pH=7, and has a functional group of, for example, any one of amino group, imino group, tertiary amine group, quaternary ammonium group, and hydrazino group. The anionic water-soluble resin is a resin that has a negative charge in the polymer in water of pH=7, and has a functional group of, for example, any one of carboxyl group, sulfone group, sulfate ester group, and phosphate ester group. Furthermore, the nonionic water-soluble resin is a resin that does not fall under the above-mentioned cationic water-soluble resin or anionic water-soluble resin, and has a functional group of, for example, any one of hydroxyl group, ether group, and amide group in the polymer.
[0028] Furthermore, these resins may contain one or more water-soluble homopolymers selected from the group consisting of acrylic polymers, urethane polymers, styrene polymers, olefin polymers, amide polymers, siloxane polymers, epoxy polymers, vinyl chloride polymers, and vinyl acetate polymers, and / or water-soluble copolymers consisting of two or more of these polymers. In particular, it is preferable that the resins contain one or more water-soluble homopolymers of acrylic polymers, styrene polymers, and olefin polymers, and / or water-soluble copolymers consisting of two or more of these polymers.
[0029] Next, in the complexing step in the method for producing metal carbide powder of the present invention, hydrogen peroxide, which will be described below, is added to the first mixed liquid thus produced to produce a second mixed liquid.
[0030] The content of hydrogen peroxide in the second mixed liquid is preferably more than 0% by mass and not more than 35% by mass, more preferably 0.001% by mass or more and not more than 30% by mass, even more preferably 0.01% by mass or more and not more than 25% by mass, and particularly preferably 0.1% by mass or more and not more than 20% by mass. Typically, the content of hydrogen peroxide may be 0.005% by mass or more, 0.05% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, or 4% by mass or more. On the other hand, the content of hydrogen peroxide may be 10% by mass or less, 5% by mass or less, 3% by mass or less, or 1% by mass or less.
[0031] The content of hydrogen peroxide in the second mixed liquid can be expressed by the molar ratio of H2O2 / metal hydroxide. The molar ratio H2O2 / metal hydroxide between hydrogen peroxide and metal hydroxide is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / metal hydroxide may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / metal hydroxide may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0032] Here, H2O2 in the molar ratio H2O2 / metal hydroxide indicates the content of H2O2 in the second mixed solution. Meanwhile, metal hydroxide in the molar ratio H2O2 / metal hydroxide indicates the content of the metal hydroxide in the second mixed solution in terms of metal atoms. In addition, when two or more types of metal hydroxides are contained, the content of the metal hydroxide in terms of metal atoms is the total content of these two or more types of metal hydroxides in terms of metal atoms.
[0033] Specifically, when the mixed metal hydroxide is tantalum hydroxide, the molar ratio H2O2 / Ta of hydrogen peroxide to tantalum is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / Ta may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0034] Furthermore, when the metal hydroxide to be mixed is niobium hydroxide, the molar ratio H2O2 / Nb of hydrogen peroxide to niobium is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / Nb may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / Nb may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0035] Furthermore, when the mixed metal hydroxides are niobium hydroxide and tantalum hydroxide, the molar ratio H2O2 / (Nb+Ta) of hydrogen peroxide to niobium and tantalum is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / (Nb+Ta) may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / (Nb+Ta) may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0036] Here, when hydrogen peroxide is added under alkaline conditions, the complexation reaction is more likely to proceed, so it is advisable to mix a metal hydroxide with an alkaline compound before adding hydrogen peroxide to produce a first mixed liquid, which is an alkaline mixed liquid.
[0037] In the complexing step in the method for producing a metal carbide powder of the present invention, an organic acid described below is added to the second mixed liquid to produce a metal carbide precursor.
[0038] Examples of organic acids include carboxylic acids, polyfunctional carboxylic acids, hydroxycarboxylic acids, and amino acids. Examples of carboxylic acids include butyric acid, formic acid, acetic acid, lauric acid, oleic acid, linoleic acid, and benzoic acid. Examples of polyfunctional carboxylic acids include oxalic acid, succinic acid, malonic acid, maleic acid, glutaric acid, and citric acid. Examples of hydroxycarboxylic acids include lactic acid, gluconic acid, tartaric acid, and malic acid. Examples of amino acids include alanine, arginine, aspartic acid, and ethylenediaminetetraacetic acid. In particular, organic acids that do not contain nitrogen atoms are preferred, such as carboxylic acids, polyfunctional carboxylic acids, and hydroxycarboxylic acids, and more preferably citric acid, tartaric acid, and lactic acid. In addition, polyfunctional carboxylic acids are more preferred, and citric acid, which is an organic acid that does not contain nitrogen atoms and is also a polyfunctional carboxylic acid, is most preferred. The organic acids also include various isomers (structural isomers, optical isomers, and the like) of the above-mentioned compounds. Furthermore, the organic acid may be one or more organic acids of the above-mentioned compounds.
[0039] The content of the organic acid in the metal carbide precursor is preferably more than 0% by mass and less than 100% by mass, more preferably 1% by mass or more and 40% by mass or less, and preferably 3% by mass or more and 15% by mass or less. Typically, the content of the organic acid may be 0.1% by mass or more, 0.5% by mass or more, 2% by mass or more, 5% by mass or more, 8% by mass or more, or 10% by mass or more. On the other hand, the content of the organic acid may be 30% by mass or less, 25% by mass or less, 20% by mass or less, or 10% by mass or less. Here, when the organic acid added to the second mixture is a mixture of two or more organic acids, the content of the organic acid is the total content of the two or more organic acids added.
[0040] The content of the organic acid in the metal carbide precursor can be expressed by the molar ratio of organic acid / metal hydroxide. It is preferable to add the organic acid so that the molar ratio of the organic acid to the metal hydroxide: organic acid / metal hydroxide is more than 0 and not more than 500. From the viewpoint of the stability of the metal carbide precursor and cost reduction, it is more preferable that it is 0.01 to 100, even more preferable that it is 0.1 to 9, and particularly preferable that it is 0.1 to 6. Typically, the molar ratio: organic acid / metal hydroxide may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / metal hydroxide may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0041] Here, the organic acid in the molar ratio of organic acid / metal hydroxide indicates the content of the organic acid in the metal carbide precursor. When two or more organic acids are contained, the content of the organic acid is the total content of these two or more organic acids. On the other hand, the metal hydroxide in the molar ratio of organic acid / metal hydroxide indicates the content of the metal hydroxide in terms of metal atoms in the metal carbide precursor. When two or more metal hydroxides are contained, the content of the metal hydroxide in terms of metal atoms is the total content of these two or more metal hydroxides in terms of metal atoms.
[0042] For example, when the metal hydroxide to be mixed is tantalum hydroxide, it is preferable to add the organic acid so that the molar ratio of the organic acid to tantalum, organic acid / Ta, is more than 0 and not more than 500, and from the viewpoint of the stability of the metal carbide precursor and cost reduction, it is more preferable that it is 0.01 to 100, even more preferable that it is 0.1 to 9, and particularly preferable that it is 0.1 to 6. Typically, the molar ratio: organic acid / Ta may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / Ta may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0043] In addition, when the metal hydroxide to be mixed is niobium hydroxide, it is preferable to add the organic acid so that the molar ratio of the organic acid to niobium: organic acid / Nb is more than 0 and not more than 500, and from the viewpoint of the stability of the metal carbide precursor and cost reduction, it is more preferable that it is 0.01 to 100, even more preferable that it is 0.1 to 9, and particularly preferable that it is 0.1 to 6. Typically, the molar ratio: organic acid / Nb may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / Nb may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0044] Furthermore, when the metal hydroxides to be mixed are niobium hydroxide and tantalum hydroxide, it is preferable to add the organic acid so that the molar ratio of the organic acid to the niobium and tantalum: organic acid / (Nb+Ta) is more than 0 and not more than 500, and from the viewpoint of the stability of the metal carbide precursor and cost reduction, it is more preferable that it is 0.01 to 100, even more preferable that it is 0.1 to 9, and particularly preferable that it is 0.1 to 6. Typically, the molar ratio: organic acid / (Nb+Ta) may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / (Nb+Ta) may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0045] The complexing step in the above-mentioned method for producing a metal carbide powder of the present invention does not require heating and can be carried out at room temperature (25° C.).
[0046] It is presumed that at least a portion of the metal carbide precursor thus produced forms a peroxo complex containing the metal element derived from the metal hydroxide.
[0047] Next, in the carbonization step in the method for producing a metal carbide powder of the present invention, the metal carbide precursor is fired to produce a metal carbide. The metal carbide precursor produced by the complexing step in the method for producing metal carbide powder of the present invention is placed in a static furnace and fired in air at a firing temperature of 1000°C or higher and 1900°C or lower for a firing time of 1 hour or higher and 12 hours or lower, thereby producing a metal carbide.
[0048] In the powdering step in the method for producing metal carbide powder of the present invention, the metal carbide is crushed to form metal carbide powder. The metal carbide produced in the carbonization step in the method for producing metal carbide powder of the present invention is crushed using a ball mill, a jet mill, a cutter mill, or the like to form the metal carbide powder of the present invention. The crushed metal carbide powder may be classified using a sieve or the like to obtain the undersize (fine particle side) metal carbide powder of the present invention. The oversize (coarse particle side) may be used after being subjected to a crushing step again and classified. The sieve used for classification is preferably one with an opening of 30 to 1000 μm.
[0049] The metal carbide powder (sample) of the present invention formed by the above-mentioned method for producing metal carbide powder of the present invention can be confirmed to be a carbide from the peaks in the X-ray diffraction pattern obtained by powder X-ray diffraction measurement according to the X-ray diffraction measurement conditions and X-ray diffraction analysis conditions described below.
[0050] =X-ray diffraction measurement conditions= Equipment: MiniFlexII (Rigaku Corporation) Measurement range (2θ): 5~90° Sampling width: 0.02° Scan speed: 2.0° / min ·X-ray: CuKα ray Voltage: 30kV ·Current: 15mA Divergence slit: 1.25° Scattering slit: 1.25° Receiving slit: 0.3 mm
[0051] =X-ray diffraction analysis conditions= Use Rigaku's data analysis software PDXL2. · Smooth the peaks with b-spline to clarify the peak tops.
[0052] The flowability of the metal carbide powder of the present invention formed by the above-mentioned method for producing a metal carbide powder of the present invention can be determined as follows. A sample of the metal carbide powder of the present invention is placed in an ABD powder property measuring device manufactured by Tsutsui Rikagaku Kikai Co., Ltd., to which a filter with a pore size of 850 μm or 1000 μm is attached, the filter is vibrated for 1 minute, and the sample that has passed through the filter is recovered. The amount of the sample recovered is then measured, and the recovery rate is calculated from the formula: Recovery rate = Recovery amount (g) / 10 g x 100, whereby the flowability of the metal carbide powder of the present invention can be determined.
[0053] The metal carbide powder of the present invention can be produced by carrying out each step in the method for producing a metal carbide powder of the present invention described above. The metal carbide powder of the present invention can also be produced by carrying out the following steps in addition to the steps described above.
[0054] The method for producing a metal carbide powder of the present invention may include a drying step of drying the metal carbide precursor. By drying the metal carbide precursor produced by the complexing step using a drying method described below, it is possible to remove excess hydrogen peroxide and ammonia contained in the metal carbide precursor.
[0055] By removing excess hydrogen peroxide from the metal carbide precursor, it is possible to suppress changes in the solution due to the evaporation of hydrogen peroxide, and it is also easier to use from a safety and legal standpoint. Specifically, if the content of hydrogen peroxide in the metal carbide precursor is 6 mass% or less, it is exempt from the Deleterious Substances Control Law, making it easier to use in terms of safety and storage methods. In addition, by removing excess ammonia contained in the metal carbide precursor, it is easier to use in terms of safety and work.
[0056] As an example of the drying step in the method for producing metal carbide powder of the present invention, the heating temperature in the drying step is preferably less than 100°C. If the heating temperature in the drying step is 25°C or higher but lower than 100°C, the excess hydrogen peroxide and ammonia contained in the metal carbide precursor will volatilize, resulting in a white peroxo complex powder. The heating temperature is more preferably 90°C or lower. The heating time is preferably 1 hour or higher but 100 hours or lower, and more preferably 5 hours or higher but 20 hours or lower.
[0057] In another example of the drying step in the method for producing metal carbide powder of the present invention, the heating temperature in the drying step is preferably 100° C. or higher. When the heating temperature in the drying step is 100° C. or more and 200° C. or less, the excess hydrogen peroxide and ammonia components contained in the metal carbide precursor are volatilized, and a greenish-white peroxo complex powder is obtained. The heating temperature is more preferably 110° C. or more. The heating time is preferably 1 hour or more and 100 hours or less, and more preferably 5 hours or more and 20 hours or less.
[0058] Furthermore, as another example of the drying step in the method for producing a metal carbide powder of the present invention, a white peroxo complex powder can be obtained by a vacuum drying method without heating. The heating time is preferably 1 hour or more and 100 hours or less, and more preferably 5 hours or more and 20 hours or less. In the case of vacuum drying, the excess hydrogen peroxide and ammonia components contained in the metal carbide precursor are not removed and remain.
[0059] The method for producing a metal carbide powder of the present invention may further include a crushing step of crushing the metal carbide precursor dried in the drying step. The peroxo complex powder, which is a metal carbide precursor dried by each of the drying steps described above, is pulverized using a ball mill, a jet mill, a cutter mill, etc. By pulverizing the peroxo complex powder, the peroxo complex powder is preferably dissolved in pure water more easily in the dissolving step.
[0060] Furthermore, the method for producing a metal carbide of the present invention is a method for producing a metal carbide in a film form using a complex polymerization method, and is characterized by having a complexing step of mixing a metal hydroxide and an alkaline compound to produce a first mixed liquid, adding hydrogen peroxide to the first mixed liquid to produce a second mixed liquid, and further adding an organic acid to the second mixed liquid to produce a metal carbide precursor; a dissolving step of producing a metal carbide intermediate in which the metal carbide precursor is dispersed in pure water; and a carbonization step of applying the metal carbide intermediate onto a substrate and firing it to form a metal carbide film containing metal carbide on the substrate. For convenience of explanation, the method for producing a metal carbide of the present invention, which includes a carbonization step of forming a metal carbide film containing a metal carbide on a substrate, will be explained as the method for producing a metal carbide film of the present invention.
[0061] In the complexing step in the method for producing a metal carbide film of the present invention, a metal hydroxide and an alkaline compound are mixed to produce a first mixed liquid, hydrogen peroxide is added to the first mixed liquid to produce a second mixed liquid, and an organic acid is further added to the second mixed liquid to produce a metal carbide precursor.
[0062] The metal carbide precursor generated in the complexing step in the method for producing a metal carbide film of the present invention is preferably in the state of a transparent solution without precipitation from the viewpoint of uniform film formation. The particle size of the metal carbide precursor is preferably small, and is preferably 1000 nm or less from the viewpoint of stability over time, more preferably 500 nm or less, and particularly preferably 100 nm or less. Typically, the particle size may be 900 nm or less, 800 nm or less, 700 nm or less, 600 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, 50 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 6 nm or less, 2 nm or less, 1 nm or less, or 0.6 nm or less. On the other hand, the particle size of the particles is preferably 1 nm or more, more preferably 2 nm or more, even more preferably 6 nm or more, particularly preferably 10 nm or more, and may be 100 nm or more, 200 nm or more, 300 nm or more, 400 nm or more, or 500 nm or more. Typically, the particle size is 10 nm or more and 800 nm or less. Typically, the particle size of the metal carbide precursor is 10 nm or more and 800 nm or less. From the viewpoint of forming a thick film, the metal carbide precursor may be in the form of an aqueous dispersion in which the metal carbide precursor is precipitated.
[0063] The particle size of the metal carbide precursor produced in the complexing step in the method for producing a metal carbide film of the present invention is a particle size (D50) measured by particle size distribution measurement using dynamic light scattering.
[0064] Here, the dynamic light scattering method is a method in which a solution such as a suspension is irradiated with light such as a laser beam to measure the light scattering intensity from a group of particles undergoing Brownian motion, and the particle size and distribution are obtained from the temporal variation of the intensity. Specifically, the particle size distribution is evaluated using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000ZS) in accordance with JIS Z 8828:2019 "Particle size analysis - dynamic light scattering method". In addition, if necessary, the measurement sample is diluted 1000 times with pure water, and the measurement sample is filtered with a filter with a pore size of 11 μm to remove dust and the like in the measurement sample immediately before measurement, and ultrasonic treatment is performed for 3 minutes with an ultrasonic cleaner (manufactured by As One Co., Ltd.: VS-100III). In addition, the liquid temperature of the measurement sample was adjusted to 25 °C. The particle size (D50) refers to the median diameter (D50), which is the particle size that shows the 50% cumulative value of the cumulative distribution curve.
[0065] The complexing step in the method for producing a metal carbide film of the present invention is the same as the complexing step in the method for producing a metal carbide powder of the present invention except for the points mentioned above, so a detailed description thereof will be omitted.
[0066] In the dissolving step in the method for producing a metal carbide film of the present invention, a metal carbide intermediate is produced by dispersing a metal carbide precursor in pure water.
[0067] Pure water is added to the metal carbide precursor obtained by the complexing step in the method for producing a metal carbide film of the present invention, and the mixture is stirred for 10 minutes to produce a metal carbide intermediate. In the carbonization step described below, it is preferable to adjust the content of the metal carbide intermediate of the present invention so that it is easy to apply when the metal carbide intermediate of the present invention is applied to a substrate, and it is preferable to adjust the solid content of the metal carbide intermediate of the present invention to be 1 mass% or more and 70 mass% or less. The dissolving step does not require heating and can be carried out at room temperature (25°C).
[0068] The solids content of the metal carbide intermediate of the present invention is preferably adjusted depending on the type and material of the base material, and is more preferably 2 mass% or more and 65 mass% or less, even more preferably 4 mass% or more and 60 mass% or less, particularly preferably 5 mass% or more and 55 mass% or less, and further particularly preferably 10 mass% or more and 50 mass% or less.
[0069] Furthermore, when tantalum hydroxide is used as the metal hydroxide, the tantalum content in the metal carbide intermediate of the present invention may typically be 5 mass% or more and 30 mass% or less, 5 mass% or more and 25 mass% or less, 5 mass% or more and 20 mass% or less, 5 mass% or more and 15 mass% or less, or 5 mass% or more and 10 mass% or less.
[0070] Here, the tantalum content in the metal carbide intermediate of the present invention is calculated by diluting the intermediate appropriately with dilute hydrochloric acid as necessary, and measuring the Ta mass fraction in Ta equivalent terms using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.
[0071] Furthermore, when niobium hydroxide is used as the metal hydroxide, the niobium content in the metal carbide intermediate of the present invention may typically be 5 mass% or more and 30 mass% or less, 5 mass% or more and 25 mass% or less, 5 mass% or more and 20 mass% or less, 5 mass% or more and 15 mass% or less, or 5 mass% or more and 10 mass% or less.
[0072] The niobium content in the metal carbide intermediate of the present invention can be calculated by measuring the Nb mass fraction calculated as Nb, in the same manner as the tantalum content described above.
[0073] In addition, in the dissolution step, if the metal carbide precursor has a suitable solid content when applied to a substrate, there is no need to adjust the solid content by adding pure water to the metal carbide precursor obtained in the complexing step.
[0074] In the carbonization step of the method for producing a metal carbide film of the present invention, a metal carbide intermediate is applied to a substrate and then fired to form a metal carbide film containing a metal carbide on the substrate. Examples of the substrate include a crucible, a furnace material, an electrode, a fiber, a filtration device, a filter, a protective tube, a heater tube, a burner nozzle, a fireproof jig, etc. Examples of the material include carbon, a metal, and a ceramic, and examples of the metal include a metal carbide, a metal oxide, and a metal nitride.
[0075] Specifically, the metal carbide intermediate obtained by the dissolving step in the method for producing a metal carbide film of the present invention is filtered, for example, with a filter having a pore size of 1 μm, and applied to the surface of a substrate using a brush or the like. The substrate to which the metal carbide intermediate has been applied is then placed in a static furnace and fired in the atmosphere at a firing temperature of 1000° C. to 1900° C. for a firing time of 1 hour to 12 hours, thereby forming a metal carbide film on the surface of the substrate. In addition to the method of applying the metal carbide intermediate to the surface of the substrate using a brush or the like, a method of spraying the metal carbide intermediate onto the surface of the substrate or a method of immersing the substrate in a container containing the metal carbide intermediate may also be used.
[0076] The metal carbide film of the present invention can be produced by carrying out each step in the method for producing a metal carbide film of the present invention described above. The metal carbide film of the present invention can also be produced by carrying out the following steps in addition to the steps described above.
[0077] In the method for producing a metal carbide film of the present invention, a drying step of drying the metal carbide precursor produced in the complexing step may be included as a preliminary step to the dissolution step of producing a metal carbide intermediate in which the metal carbide precursor is dispersed in pure water. By drying the metal carbide precursor produced by the complexing step using the drying method described above, it is possible to remove excess hydrogen peroxide and ammonia contained in the metal carbide precursor.
[0078] By removing excess hydrogen peroxide from the metal carbide precursor, when pure water is added to the metal carbide precursor in the carbonization step and the generated metal carbide intermediate is applied to the surface of the substrate, foaming does not occur and the intermediate can be applied uniformly. In addition, by removing excess ammonia contained in the metal carbide precursor, the metal carbide precursor becomes easier to use in terms of safety and workability.
[0079] The drying step in the method for producing a metal carbide film of the present invention is the same as the drying step in the method for producing a metal carbide powder of the present invention described above, and therefore a detailed description thereof will be omitted.
[0080] The method for producing a metal carbide film of the present invention may further include a crushing step of crushing the metal carbide precursor dried in the drying step, as in the method for producing a metal carbide powder of the present invention described above. Note that the crushing step in the method for producing a metal carbide film of the present invention is the same as the crushing step in the method for producing a metal carbide powder of the present invention described above, and therefore will not be described here.
[0081] Furthermore, the method for producing a metal carbide precursor of the present invention is a method for producing a metal carbide precursor using a complex polymerization method, and is characterized by having a complexation step of mixing a metal hydroxide and an alkaline compound to produce a first mixed liquid, adding hydrogen peroxide to the first mixed liquid to produce a second mixed liquid, and further adding an organic acid to the second mixed liquid to produce a metal carbide precursor.
[0082] The complexing step in the method for producing a metal carbide precursor of the present invention is the same as the complexing step in the method for producing a metal carbide of the present invention described above, and therefore a detailed description thereof will be omitted.
[0083] The method for producing a metal carbide precursor of the present invention may further include a drying step of drying the metal carbide precursor produced in the complexing step. Here, the drying step in the method for producing a metal carbide precursor of the present invention is the same as the drying step in the method for producing a metal carbide precursor of the present invention described above, and therefore a description thereof will be omitted.
[0084] Furthermore, the method for producing a metal carbide intermediate of the present invention is a method for producing a metal carbide intermediate using a complex polymerization method, and is characterized by comprising a complexing step of mixing a metal hydroxide and an alkaline compound to produce a first mixed liquid, adding hydrogen peroxide to the first mixed liquid to produce a second mixed liquid, and further adding an organic acid to the second mixed liquid to produce a metal carbide precursor, and a dissolving step of dispersing the metal carbide precursor in pure water to produce a metal carbide intermediate.
[0085] The complexing step and the dissolving step in the method for producing a metal carbide intermediate of the present invention are the same as the complexing step and the dissolving step in the method for producing a metal carbide of the present invention described above, and therefore detailed description thereof will be omitted.
[0086] The method for producing a metal carbide intermediate of the present invention may further include a drying step of drying the metal carbide precursor produced in the complexing step. Here, the drying step in the method for producing a metal carbide intermediate of the present invention is the same as the drying step in the method for producing a metal carbide of the present invention described above, and therefore a description thereof will be omitted.
[0087] In the method for producing a metal carbide intermediate of the present invention, the heating temperature in the drying step is preferably less than 100° C., similar to the drying step in the method for producing a metal carbide of the present invention described above.
[0088] In the method for producing a metal carbide intermediate of the present invention, the heating temperature in the drying step is preferably 100° C. or higher, similarly to the drying step in the method for producing a metal carbide of the present invention described above.
[0089] Furthermore, the method for producing a metal carbide intermediate of the present invention may be vacuum drying without heating, similar to the drying step in the method for producing a metal carbide of the present invention described above.
[0090] The method for producing a metal carbide intermediate of the present invention is characterized by further comprising a crushing step of crushing the metal carbide precursor dried in the drying step. Here, the crushing step in the method for producing a metal carbide intermediate of the present invention is the same as the crushing step in the method for producing a metal carbide of the present invention described above, and therefore a description thereof will be omitted.
[0091] The metal carbide powder of the present invention has a specific surface area of 1 m2 measured by the BET method. 2 / g or more, and the circularity is 0.78 or more. The metal carbide powder of the present invention has a specific surface area of 1 m2 as measured by the BET method. 2 When the particle diameter is 0.5 mm or more and the circularity is 0.78 or more, even if the particles are very fine, they have high fluidity.
[0092] The metal carbide powder of the present invention has a specific surface area of 1 m2 as measured by the BET method. 2 When the specific surface area of the metal carbide powder of the present invention is 2 m / g or more, the void ratio in the powder packed bed is reduced, and the reactivity with other substances is increased when the powder is used as an additive. 2 / g or more is more preferable, 2 It is more preferable that the molecular weight is 1 / g or more.
[0093] Here, the specific surface area of the metal carbide powder of the present invention as measured by the BET method can be measured using a fully automatic specific surface area measuring device (Macsorb HM-1230 type) in accordance with JIS Z8830.
[0094] In addition, the metal carbide powder of the present invention is preferably one having a circularity of 0.78 or more, since the void ratio in the powder packed bed is reduced and the reactivity with other substances is increased when used as an additive. The circularity of the metal carbide powder of the present invention is more preferably 0.8 or more, and even more preferably 0.9 or more. On the other hand, the upper limit of the circularity is not particularly limited, and may be 1 or less.
[0095] Here, the circularity of the metal carbide powder of the present invention is calculated by "circularity = 1 / major axis × minor axis", and the arithmetic average value of the circularity of multiple particles is taken as the "circularity". Here, the "major axis" and "minor axis" are calculated as follows. Using a scanning electron microscope (SEM) (Hitachi High-Technologies Corporation: S-4800), an SEM image of the primary particles of the metal carbide powder of the present invention is measured at a magnification at which the primary particles of the metal carbide powder of the present invention can be measured. Then, using ImageJ, an image analysis software, the "major axis" and "minor axis" of 20 randomly selected particles are measured.
[0096] Moreover, the metal carbide powder of the present invention preferably has a primary particle size of 0.7 μm or less as measured by the BET method and a circularity of 0.78 or more. The metal carbide powder of the present invention has a primary particle size of 0.7 μm or less as measured by the BET method and a circularity of 0.78 or more, and has high fluidity even in the case of extremely fine particles.
[0097] The metal carbide powder of the present invention preferably has a primary particle size of 0.7 μm or less by the BET method, from the viewpoint of reducing the void ratio in the powder packed bed and increasing the reactivity with other substances when used as an additive. The primary particle size of the metal carbide powder of the present invention by the BET method is more preferably 0.4 μm or less, and even more preferably 0.2 μm or less.
[0098] Here, the primary particle diameter D of the metal carbide powder of the present invention as determined by the BET method is calculated by the following formula (1).
[0099]
number
[0100] In the formula (1), "D" represents the primary particle diameter (μm) of the metal carbide powder of the present invention, and "S" represents the specific surface area (m 2 / g, "ρ" is the density of the metal carbide of the present invention (g / cm 3 For example, the density of tantalum carbide (TaC) is 13.9 (g / cm 3 ), and the density of niobium carbide (NbC) is 8.57 (g / cm3 ).
[0101] The metal carbide powder of the present invention preferably contains tantalum carbide, niobium carbide, titanium carbide, tungsten carbide, molybdenum carbide, zirconium carbide, or the like, and more preferably contains tantalum carbide or niobium carbide.
[0102] In addition, the metal carbide powder of the present invention preferably has a chlorine content of 100 ppm or less, from the viewpoint of no residual hydrogen peroxide in the metal carbide powder of the present invention. The metal carbide powder of the present invention more preferably has a chlorine content of 50 ppm or less, and even more preferably has a chlorine content of 25 ppm or less. In this specification, unless otherwise specified, "ppm" refers to "ppm by mass".
[0103] Here, the chlorine content in the metal carbide powder of the present invention can be measured by a combustion ion chromatography method. Specifically, an appropriate amount of sample is collected on a ceramic board, and the sample is heated under an argon (Ar) atmosphere at 1000°C for 10 minutes using a combustion ion chromatography (Nitto Seiko Analytech Co., Ltd.: AQF-2100H), and the amount of chlorine generated is measured, whereby the chlorine content in the metal carbide powder of the present invention can be obtained.
[0104] In addition, the metal carbide powder of the present invention is preferably such that the nitrogen content in the metal carbide powder is 1000 ppm or less, from the viewpoint that no alkaline compound, such as ammonia water, remains in the metal carbide powder of the present invention. The metal carbide powder of the present invention is more preferably such that the nitrogen content in the metal carbide powder is 800 ppm or less, and even more preferably such that the nitrogen content is 500 ppm or less, 250 ppm or less, 100 ppm or less, 50 ppm or less, or 25 ppm or less.
[0105] Here, the nitrogen content in the metal carbide powder of the present invention can be measured by a thermal conductivity method using an oxygen / nitrogen analyzer (ON836 manufactured by LECO). Specifically, an appropriate amount of sample is sealed in a Ni capsule, and the nitrogen content in the metal carbide powder of the present invention can be determined by the thermal conductivity method using the oxygen / nitrogen analyzer.
[0106] In addition, the metal carbide powder of the present invention may contain components derived from metal hydroxides, such as components derived from tantalum or tantalum hydroxide, or components derived from niobium or niobium hydroxide (hereinafter referred to as "other components"), within a range that does not impair the action and effect of the metal carbide powder. Examples of other components include Li, Mg, Si, Ca, Mn, Ni, Cu, Zn, Sr, Ba, etc. However, the other components are not limited to these. The content of other components in the metal carbide powder of the present invention is preferably less than 5 mass% in elemental terms (metal element or nonmetal element terms), more preferably less than 4 mass%, and even more preferably less than 3 mass%. It is assumed that the metal carbide powder of the present invention contains unavoidable impurities, not intentionally. The content of unavoidable impurities is preferably less than 0.01 mass%.
[0107] The cemented carbide tool of the present invention is characterized by containing the above-mentioned metal carbide powder of the present invention. The cemented carbide tool of the present invention contains the metal carbide powder of the present invention, and therefore, even though it is an extremely fine particle, it has high fluidity, high mixability with tungsten carbide, and excellent subsequent reactivity. It also has the properties required of a cemented carbide tool, such as chipping resistance, plastic deformation resistance, and wear resistance.
[0108] The metal carbide intermediate dispersion liquid of the present invention is characterized in that it contains a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid, and that the particle size (D50) of particles in the metal carbide intermediate dispersion liquid, as determined by particle size distribution measurement using a dynamic light scattering method, is 1000 nm or less.
[0109] The metal compound is preferably a hydroxide, chloride or alkoxide of tantalum, niobium, titanium, zirconium, hafnium, bismuth, molybdenum or tungsten.
[0110] The metal compound is more preferably a metal hydroxide, such as hydroxides of tantalum, niobium, titanium, zirconium, hafnium, bismuth, molybdenum, and tungsten, and is particularly preferably tantalum hydroxide and / or niobium hydroxide.
[0111] The alkaline compound is preferably one or more alkaline compounds selected from ammonia, sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, and organic nitrogen compounds. The organic nitrogen compounds include, for example, amine compounds, quaternary ammonium compounds, guanidine compounds, and azole compounds, and are preferably amine compounds or quaternary ammonium compounds, and more preferably methylamine, dimethylamine, tetramethylammonium hydroxide (TMAH), or tetraethylammonium hydroxide (TEAH). The alkaline compound is particularly preferably ammonia.
[0112] The alkaline compound content in the metal carbide intermediate dispersion of the present invention is preferably more than 0% by mass and less than 50% by mass, and more preferably 0.01% by mass or more and 4% by mass or less. From the viewpoint of reactivity and dispersibility, it is desirable to have a high content of the alkaline compound. On the other hand, since it is a volatile component, a low content is desirable from the viewpoint of suppressing volatilization during film formation in a later process. Typically, the alkaline compound content may be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, or 10% by mass or more. On the other hand, the alkaline compound content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, or 10% by mass or less.
[0113] The content of the alkaline compound in the metal carbide intermediate dispersion of the present invention can be expressed by the molar ratio of the alkaline compound / metal compound. The molar ratio of the alkaline compound / metal compound is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of the alkaline compound / metal compound may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of the alkaline compound / metal compound may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0114] Here, the alkaline compound in the alkaline compound / metal compound molar ratio indicates the content of the alkaline compound in the metal carbide intermediate dispersion liquid of the present invention. In addition, when the alkaline compound contained in the metal carbide intermediate dispersion liquid of the present invention is two or more types, the content of the alkaline compound is the total content of these two or more types of alkaline compounds. On the other hand, the metal compound in the alkaline compound / metal compound molar ratio indicates the content of the metal compound in the metal carbide intermediate dispersion liquid of the present invention in terms of metal atoms. In addition, when the metal carbide intermediate dispersion liquid of the present invention is two or more types, the content of the metal compound in terms of metal atoms is the total content of these two or more types of metal compounds in terms of metal atoms.
[0115] When the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is tantalum hydroxide, the molar ratio of the alkaline compound / Ta is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of the alkaline compound / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of the alkaline compound / Ta may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0116] In addition, when the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is niobium hydroxide, the molar ratio of the alkaline compound / Nb is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of the alkaline compound / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of the alkaline compound / Nb may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0117] Furthermore, when the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is niobium hydroxide and tantalum hydroxide, the molar ratio of the alkaline compound to niobium and tantalum: alkaline compound / (Nb+Ta) is preferably more than 0 and not more than 100, more preferably 0.001 to 100, even more preferably 0.01 to 50, particularly preferably 0.1 to 30, and more particularly preferably 4 to 20. Typically, the molar ratio of the alkaline compound / (Nb+Ta) may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of the alkaline compound / (Nb+Ta) may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0118] In the case where the alkaline compound is, for example, ammonia, the ammonia content is preferably more than 0% by mass and less than 50% by mass, and more preferably 0.01% by mass or more and 4% by mass or less. From the viewpoint of reactivity and dispersibility, it is desirable to have a high ammonia content. On the other hand, since it is a volatile component, a low ammonia content is desirable from the viewpoint of suppressing volatilization during film formation in a later process. Typically, the ammonia content may be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, 3% by mass or more, 5% by mass or more, 8% by mass or more, or 10% by mass or more. On the other hand, the ammonia content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, or 10% by mass or less.
[0119] The content of ammonia contained in the metal carbide intermediate dispersion liquid of the present invention can be expressed by the molar ratio of NH3 / metal compound. The molar ratio of NH3 / metal compound is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of NH3 / metal compound may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / metal compound may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0120] When the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is tantalum hydroxide, the molar ratio of NH3 / Ta is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of NH3 / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / Ta may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0121] In addition, when the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is niobium hydroxide, the molar ratio of NH3 / Nb is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of NH3 / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / Nb may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0122] Furthermore, when the metal compounds contained in the metal carbide intermediate dispersion liquid of the present invention are niobium hydroxide and tantalum hydroxide, the molar ratio of ammonia to niobium and tantalum: NH3 / (Nb+Ta) is preferably more than 0 and not more than 100, more preferably 0.001 or more and not more than 100, even more preferably 0.01 or more and not more than 50, particularly preferably 0.1 or more and not more than 30, and more particularly preferably 4 or more and not more than 20. Typically, the molar ratio of NH3 / (Nb+Ta) may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio of NH3 / (Nb+Ta) may be 15 or less, 10 or less, 8 or less, 5 or less, 4 or less, 3 or less, 2 or less, 1 or less, 0.5 or less, or 0.1 or less.
[0123] Incidentally, the amount of the alkaline compound contained in the metal carbide intermediate dispersion liquid of the present invention can be reduced by replenishing the solvent that has evaporated by heating or the like after preparation of the metal carbide intermediate dispersion liquid.
[0124] The content of hydrogen peroxide in the metal carbide intermediate dispersion of the present invention is preferably more than 0% by mass and not more than 35% by mass, more preferably 0.001% by mass or more and not more than 30% by mass, even more preferably 0.01% by mass or more and not more than 25% by mass, and particularly preferably 0.1% by mass or more and not more than 20% by mass. Typically, the content of hydrogen peroxide may be 0.005% by mass or more, 0.05% by mass or more, 0.5% by mass or more, 1% by mass or more, 2% by mass or more, or 4% by mass or more. On the other hand, the content of hydrogen peroxide may be 10% by mass or less, 5% by mass or less, 3% by mass or less, or 1% by mass or less.
[0125] The content of hydrogen peroxide in the metal carbide intermediate dispersion liquid of the present invention can be expressed by the molar ratio of H2O2 / metal compound. The molar ratio H2O2 / metal compound between hydrogen peroxide and the metal compound is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / metal compound may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / metal compound may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0126] Here, H2O2 in the molar ratio H2O2 / metal compound indicates the content of H2O2 in the metal carbide intermediate dispersion liquid of the present invention. Meanwhile, the metal compound in the molar ratio H2O2 / metal compound indicates the content of the metal compound in terms of metal atoms in the metal carbide intermediate dispersion liquid of the present invention. Furthermore, when the metal carbide intermediate dispersion liquid of the present invention contains two or more types of metal compounds, the content of the metal compound in terms of metal atoms is the total content of these two or more types of metal compounds in terms of metal atoms.
[0127] When the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is, for example, tantalum hydroxide, the molar ratio H2O2 / Ta of hydrogen peroxide to tantalum is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / Ta may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / Ta may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0128] Furthermore, when the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is, for example, niobium hydroxide, the molar ratio H2O2 / Nb of hydrogen peroxide to niobium is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / Nb may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / Nb may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0129] Furthermore, when the metal compound contained in the metal carbide intermediate dispersion liquid of the present invention is, for example, niobium hydroxide and tantalum hydroxide, the molar ratio H2O2 / (Nb+Ta) of hydrogen peroxide to niobium and tantalum is preferably more than 0 and not more than 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. Typically, the molar ratio H2O2 / (Nb+Ta) may be 0.005 or more, 0.05 or more, or 0.5 or more. On the other hand, the molar ratio H2O2 / (Nb+Ta) may be 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.
[0130] The content of hydrogen peroxide is preferably small from the viewpoint of safety (volatility, volatility due to reaction with other materials), while the above-mentioned content and molar ratio of hydrogen peroxide provide good dispersibility.
[0131] Examples of organic acids include carboxylic acids, polyfunctional carboxylic acids, hydroxycarboxylic acids, and amino acids. Examples of carboxylic acids include butyric acid, formic acid, acetic acid, lauric acid, oleic acid, linoleic acid, and benzoic acid. Examples of polyfunctional carboxylic acids include oxalic acid, succinic acid, malonic acid, maleic acid, glutaric acid, and citric acid. Examples of hydroxycarboxylic acids include lactic acid, gluconic acid, tartaric acid, and malic acid. Examples of amino acids include alanine, arginine, aspartic acid, and ethylenediaminetetraacetic acid. In particular, organic acids that do not contain nitrogen atoms are preferred, such as carboxylic acids, polyfunctional carboxylic acids, and hydroxycarboxylic acids, and more preferably citric acid, tartaric acid, and lactic acid. In addition, polyfunctional carboxylic acids are more preferred, and citric acid, which is an organic acid that does not contain nitrogen atoms and is also a polyfunctional carboxylic acid, is most preferred. The organic acids also include various isomers (structural isomers, optical isomers, and the like) of the above-mentioned compounds. Furthermore, the organic acid may be one or more organic acids of the above-mentioned compounds.
[0132] The content of the organic acid is preferably more than 0% by mass and less than 100% by mass, more preferably 1% by mass or more and 40% by mass or less, and preferably 3% by mass or more and 15% by mass or less. Typically, the content of the organic acid may be 0.1% by mass or more, 0.5% by mass or more, 2% by mass or more, 5% by mass or more, 8% by mass or more, or 10% by mass or more. On the other hand, the content of the organic acid may be 30% by mass or less, 25% by mass or less, 20% by mass or less, or 10% by mass or less. Here, when the metal carbide intermediate dispersion liquid of the present invention contains two or more organic acids, the content of the organic acid is the total content of these two or more organic acids.
[0133] The content of the organic acid in the metal carbide intermediate dispersion of the present invention can be expressed by the molar ratio of organic acid / metal compound. It is preferable to add the organic acid so that the molar ratio of the organic acid to the metal compound: organic acid / metal compound is more than 0 and not more than 500. From the viewpoint of the stability and cost reduction of the metal carbide intermediate dispersion of the present invention, it is more preferable that it is 0.01 to 100, even more preferable that it is 0.1 to 9, and particularly preferable that it is 0.1 to 6. Typically, the molar ratio: organic acid / metal compound may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / metal compound may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0134] Here, the organic acid in the molar ratio: organic acid / metal compound indicates the content of the organic acid in the metal carbide intermediate dispersion liquid of the present invention. When the metal carbide intermediate dispersion liquid of the present invention contains two or more organic acids, the content of the organic acid is the total content of these two or more organic acids. On the other hand, the metal compound in the molar ratio: organic acid / metal compound indicates the content of the metal compound in terms of metal atoms in the metal carbide intermediate dispersion liquid of the present invention. When the metal carbide intermediate dispersion liquid of the present invention contains two or more metal compounds, the content of the metal compound in terms of metal atoms is the total content of these two or more metal compounds in terms of metal atoms.
[0135] When the metal hydroxide contained in the metal carbide intermediate dispersion liquid of the present invention is tantalum hydroxide, it is preferable to add an organic acid so that the molar ratio of the organic acid to tantalum, organic acid / Ta, is more than 0 and not more than 500, and from the viewpoint of the stability and cost reduction of the metal carbide intermediate dispersion liquid of the present invention, it is more preferable that it is 0.01 to 100, further preferably 0.1 to 9, and particularly preferably 0.1 to 6. Typically, the molar ratio: organic acid / Ta may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / Ta may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0136] In the case of niobium hydroxide contained in the metal carbide intermediate dispersion of the present invention, it is preferable to add an organic acid so that the molar ratio of the organic acid to niobium: organic acid / Nb is more than 0 and not more than 500. From the viewpoint of the stability and cost reduction of the metal carbide intermediate dispersion of the present invention, it is more preferable that it is 0.01 to 100, even more preferable that it is 0.1 to 9, and particularly preferable that it is 0.1 to 6. Typically, the molar ratio: organic acid / Nb may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / Nb may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0137] Furthermore, when the metal hydroxide contained in the metal carbide intermediate dispersion liquid of the present invention is niobium hydroxide and tantalum hydroxide, it is preferable to add the organic acid so that the molar ratio of the organic acid to the niobium and tantalum: organic acid / (Nb+Ta) is more than 0 and not more than 500, and from the viewpoint of the stability and cost reduction of the metal carbide intermediate dispersion liquid of the present invention, it is more preferable that it is 0.01 to 100, further preferably 0.1 to 9, and particularly preferably 0.1 to 6. Typically, the molar ratio: organic acid / (Nb+Ta) may be 0.005 or more, 0.5 or more, 1 or more, 2 or more, 3 or more, or 5 or more. On the other hand, the molar ratio: organic acid / (Nb+Ta) may be 200 or less, 50 or less, 40 or less, 30 or less, 20 or less, 10 or less, 8 or less, or 5 or less.
[0138] Furthermore, the metal carbide intermediate dispersion liquid of the present invention may have water, an organic solvent, or a mixed solvent thereof as a solvent. In addition, examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, and the like, and may be a mixture of these organic solvents and pure water. In addition, examples of the alcohol solvent include alcohols having 5 or less carbon atoms (methanol, ethanol, n-propanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol), high boiling point solvents, acetone, and the like. It is preferable that the above-mentioned solvents are compatible with water. Examples of the high boiling point solvent include polyhydric alcohol solvents and glycol solvents. It is preferable that the solvent contained in the metal carbide intermediate dispersion liquid of the present invention is water, in that high dispersibility can be maintained.
[0139] The solvent may contain a resin such as a polyolefin compound or a polyvinyl compound. The resin added to the solvent may be an anionic water-soluble resin and / or a nonionic water-soluble resin.
[0140] As described above, the metal carbide intermediate dispersion of the present invention contains a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid, and it is presumed that at least a portion of them form a peroxo complex containing a metal element derived from the metal compound.
[0141] In addition, in the metal carbide intermediate dispersion of the present invention, the particle size (D50) of the particles in the metal carbide intermediate dispersion measured by a particle size distribution using a dynamic light scattering method is preferably 1000 nm or less from the viewpoint of stability over time, more preferably 500 nm or less, and particularly preferably 100 nm or less. Typically, the particle size (D50) may be 900 nm or less, 800 nm or less, 700 nm or less, 600 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, 50 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 6 nm or less, 2 nm or less, 1 nm or less, or 0.6 nm or less. On the other hand, the particle size (D50) of the particles in the metal carbide intermediate dispersion liquid of the present invention is preferably 1 nm or more, more preferably 2 nm or more, even more preferably 6 nm or more, particularly preferably 10 nm or more, and may further be 100 nm or more, 200 nm or more, 300 nm or more, 400 nm or more, or 500 nm or more. Typically, the particle size (D50) of the particles in the metal carbide intermediate dispersion liquid of the present invention is 10 nm or more and 800 nm or less.
[0142] Specifically, the particle size distribution is evaluated using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000ZS) in accordance with JIS Z 8828:2019 "Particle size analysis-dynamic light scattering method". In addition, if necessary, the sample is diluted 1000 times with pure water to be used as a measurement sample, and the measurement sample is filtered with a filter having a pore size of 11 μm to remove dust and the like in the measurement sample immediately before measurement, and ultrasonic treatment is performed for 3 minutes with an ultrasonic cleaner (manufactured by AS ONE Co., Ltd.: VS-100III). Furthermore, the liquid temperature of the measurement sample was adjusted to 25 ° C. The particle size (D50) of the particles in the metal carbide intermediate dispersion liquid of the present invention refers to the median size (D50), which is the particle size showing the 50% cumulative value of the cumulative distribution curve. Furthermore, in this specification, unless otherwise specified, the "particle diameter (D50)" includes both the particle diameter (D50) of the particles in the metal carbide intermediate dispersion liquid of the present invention adjusted to a liquid temperature of 25°C immediately after production, and the particle diameter (D50) of the particles in the metal carbide intermediate dispersion liquid of the present invention after it has been left to stand for two weeks or three weeks from the day the metal carbide intermediate dispersion liquid of the present invention is produced in an incubator set at room temperature of 25°C.
[0143] The metal carbide intermediate dispersion liquid of the present invention is characterized in that it contains a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid, and that the maximum light transmittance of the metal carbide intermediate dispersion liquid in a wavelength region of 350 nm to 750 nm is 70% or more.
[0144] The metal carbide intermediate dispersion liquid of the present invention contains a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid as described above. Note that the metal carbide intermediate dispersion liquid of the present invention may contain water, an organic solvent, or a mixed solvent thereof as a solvent as described above.
[0145] In addition, the metal carbide intermediate dispersion liquid of the present invention is preferably such that the maximum light transmittance in the wavelength region of 350 nm to 750 nm is 70% or more, since the degree of dispersion is high and the uniformity of the liquid components is excellent. The maximum light transmittance in the wavelength region of 350 nm to 750 nm is more preferably 85% or more, even more preferably 90% or more, and most preferably 100%. Typically, the maximum light transmittance may be 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 90% or more, 98% or more, or 99% or more.
[0146] Furthermore, the metal carbide intermediate dispersion liquid of the present invention preferably has a light transmittance of 70% or more at any one or more wavelengths of 350 nm, 450 nm, 550 nm, 650 nm, and 750 nm, more preferably 85% or more, even more preferably 90% or more, and most preferably 100%. Typically, the light transmittance at any one or more wavelengths of 350 nm, 450 nm, 550 nm, 650 nm, and 750 nm may be 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 90% or more, 98% or more, or 99% or more.
[0147] Furthermore, the metal carbide intermediate dispersion liquid of the present invention preferably has a light transmittance in the wavelength region of 350 nm to 750 nm of 70% or more, more preferably 85% or more, even more preferably 90% or more, and most preferably 100%. Typically, the light transmittance in the wavelength region of 350 nm to 750 nm may be 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 90% or more, 98% or more, or 99% or more.
[0148] In addition, due to measurement errors, etc., the measured value of the light transmittance may exceed 100%, but since the theoretical upper limit is 100%, when the measured value exceeds 100%, it is considered to be 100%. In this way, a liquid in which the maximum light transmittance in the wavelength region of 350 nm to 750 nm of the metal carbide intermediate dispersion liquid of the present invention is 70% or more is defined as the "metal carbide intermediate dispersion liquid" of the present invention. Furthermore, in this specification, unless otherwise specified, the "light transmittance" includes both the light transmittance of the metal carbide intermediate dispersion liquid of the present invention adjusted to a liquid temperature of 25°C immediately after production, and the light transmittance of the metal carbide intermediate dispersion liquid of the present invention left to stand for 2 weeks or 3 weeks from the day of production in an incubator set at room temperature of 25°C.
[0149] Here, the above-mentioned light transmittance is measured for the metal carbide intermediate dispersion liquid of the present invention using a spectrophotometer in accordance with the following transmittance measurement conditions.
[0150] =Light transmittance measurement conditions= Measurement equipment: UV-Vis-NIR spectrophotometer UH4150 (manufactured by Hitachi High-Tech Science Corporation) Measurement mode: Wavelength scan Data mode: %T (transparent) Measurement wavelength range: 200nm~2000nm Scan speed: 600nm / min Sampling interval: 2nm
[0151] In the present invention, the "dispersion" is not limited to a dispersion in which a solute is dispersed or mixed in a solvent in a monomolecular state, but also includes an aggregate in which a plurality of molecules are attracted to each other by intermolecular interactions, such as (1) polymer molecules, (2) solvated molecules, (3) molecular clusters, and (4) colloidal particles dispersed in a solvent.
[0152] The metal carbide intermediate dispersion liquid of the present invention is characterized in that it has a pH of 3.0 or more and 10.0 or less. The pH of the metal carbide intermediate dispersion of the present invention is preferably 3.0 or more and 10.0 or less, in terms of stabilizing the polyacid ions contained in the dispersion. The pH of the metal carbide intermediate dispersion of the present invention is more preferably 4.0 or more and 7.0 or less, and further preferably 4.7 or more and 6.5 or less. Typically, the pH may be 5.0 or more, 6.0 or more, or 6.5 or more. On the other hand, the pH may be 9.0 or less, or 8.0 or less. In this specification, unless otherwise specified, "pH" refers to both the pH of the metal carbide intermediate dispersion of the present invention adjusted to a liquid temperature of 25°C immediately after production, and the pH of the metal carbide intermediate dispersion of the present invention after being left to stand for 2 weeks or 3 weeks from the day of production of the metal carbide intermediate dispersion of the present invention in an incubator set at room temperature of 25°C.
[0153] Here, the pH of the metal carbide intermediate dispersion liquid of the present invention is measured by immersing an electrode (manufactured by HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (manufactured by HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) in the metal carbide intermediate dispersion liquid of the present invention, and after confirming that the liquid temperature has stabilized at 25°C.
[0154] The metal carbide intermediate dispersion liquid of the present invention is characterized in that the molar ratio of the organic acid to the metal compound is greater than 0 and 500, the molar ratio of the hydrogen peroxide to the metal compound is greater than 0 and 10, and the molar ratio of the alkaline compound to the metal compound is greater than 0 and 100. In terms of stability and dispersibility of the metal carbide intermediate dispersion liquid of the present invention, it is preferable that the molar ratio of the organic acid to the metal compound is greater than 0 and 500, the molar ratio of the hydrogen peroxide to the metal compound is greater than 0 and 10, and the molar ratio of the alkaline compound to the metal compound is greater than 0 and 100.
[0155] The molar ratio of the organic acid to the metal compound is preferably greater than 0 to 500, more preferably 0.01 to 100, even more preferably 0.1 to 9, and particularly preferably 0.1 to 6. The molar ratio of the hydrogen peroxide to the metal compound is preferably greater than 0 to 10, more preferably 0.001 to 3, and even more preferably 0.01 to 1. The molar ratio of the alkaline compound to the metal compound is preferably greater than 0 to 100, more preferably 0.001 to 100, even more preferably 0.01 to 50, particularly preferably 0.1 to 30, and even more particularly preferably 4 to 20.
[0156] Here, the molar ratio of the organic acid to the metal compound, the molar ratio of the hydrogen peroxide to the metal compound, and the molar ratio of the alkaline compound to the metal compound can be determined by calculating the metal compound content, the organic acid content, the hydrogen peroxide content, and the alkaline compound content according to the following measurement methods.
[0157] The metal compound content in the metal carbide intermediate dispersion of the present invention can be calculated by diluting the dispersion appropriately with dilute hydrochloric acid as necessary, and measuring the metal atomic mass fraction in terms of metal atoms in the metal compound using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.
[0158] Methods for measuring the organic acid content in the metal carbide intermediate dispersion liquid of the present invention include gas chromatography (GC), liquid chromatography (LC), mass spectrometry (MS), gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), etc.
[0159] The hydrogen peroxide content in the metal carbide intermediate dispersion of the present invention can be confirmed by, for example, using a standard addition method to measure the relative intensity of absorbance with respect to a standard solution of hydrogen peroxide. Specifically, a wavelength region in which a change in absorbance due to the formation of a peroxo complex is observed is found from the UV-visible absorption spectrum of a standard solution containing hydrogen peroxide at a known concentration, for example 1 mass %, and a standard solution to which hydrogen peroxide is not added, and if the difference in absorbance between the standard solution to which hydrogen peroxide is not added and a sample with an unknown hydrogen peroxide concentration in that wavelength region is less than 1%, it can be confirmed that the sample with an unknown hydrogen peroxide concentration does not substantially contain hydrogen peroxide. When hydrogen peroxide is contained in the dispersion, hydrogen peroxide reacts with a polyacid of a metal element to form a peroxo complex, so that it can be confirmed that hydrogen peroxide is not contained in the dispersion by confirming the difference in absorbance with the standard solution to which hydrogen peroxide is not added as described above. In addition to the above-mentioned standard addition method, hydrogen peroxide in the dispersion may be qualitatively and quantitatively analyzed by, for example, using a commercially available hydrogen peroxide measurement kit, adding a reagent that undergoes a color reaction with hydrogen peroxide to the dispersion and measuring the color development, or by adding a reagent that undergoes a fluorescent reaction with hydrogen peroxide to the dispersion and measuring the light emission.
[0160] The content of an alkaline compound in the metal carbide intermediate dispersion of the present invention, for example, the ammonia content, can be measured by adding sodium hydroxide to the dispersion, distilling and separating ammonia, and quantifying the ammonia content with an ion meter, quantifying the N2 content in a gasified sample with a thermal conductivity meter, or the Kjeldahl method. In particular, the method of quantifying the ammonia content with an ion meter is preferred. In addition, the content of an organic nitrogen compound can be measured by gas chromatography (GC), ion chromatography, gas chromatography mass spectrometry (GC-MS), or the like. For example, the content of one or more organic nitrogen compounds selected from sodium hydroxide, potassium hydroxide, lithium hydroxide, and calcium hydroxide can be measured in accordance with JIS K0116:2014 using ICP emission spectrometry.
[0161] In this manner, the molar ratio of the organic acid to the metal compound, the molar ratio of the hydrogen peroxide to the metal compound, and the molar ratio of the alkaline compound to the metal compound can be calculated from the calculated metal compound content, organic acid content, hydrogen peroxide content, and alkaline compound content.
[0162] The metal carbide intermediate dispersion of the present invention is characterized in that the metal carbide intermediate dispersion has a tantalum content calculated as Ta of 0.4 mass % or more, or a niobium content calculated as Nb of 0.35 mass % or more. The tantalum content in terms of Ta in the metal carbide intermediate dispersion liquid of the present invention is preferably 0.4 mass% or more, or the niobium content in terms of Nb in terms of 0.35 mass% or more, in terms of the thickness of the metal carbide film when formed. The tantalum content in terms of Ta in the metal carbide intermediate dispersion liquid of the present invention is more preferably 10 mass% or more, and even more preferably 20 mass% or more. The niobium content in terms of Nb in the metal carbide intermediate dispersion liquid of the present invention is more preferably 20 mass% or more, and even more preferably 30 mass% or more.
[0163] As described above, the tantalum content or the niobium content in the metal carbide intermediate dispersion liquid of the present invention can be calculated by measuring the Ta mass fraction in Ta equivalent or the Nb mass fraction in Nb equivalent using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.
[0164] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention
[0165] The method for producing metal carbide of the present invention can produce a metal carbide powder that is extremely fine and exhibits high fluidity. The metal carbide of the present invention exhibits high fluidity even in the case of extremely fine particles. Furthermore, the metal carbide intermediate dispersion of the present invention is a dispersion that has high dispersibility and does not produce precipitates even after a long period of time has elapsed. [Brief description of the drawings]
[0166] [Figure 1] 1 is a table showing physical property values of metal carbide intermediate dispersions according to Examples 3 to 10 and Comparative Examples 8 to 10. [Diagram 2] 1 is a table showing the measurement results of metal carbide intermediate dispersions according to Examples 3 to 10 and Comparative Examples 8 to 10. BEST MODE FOR CARRYING OUT THEINVENTION
[0167] The metal carbide according to the embodiment of the present invention will be further described below with reference to the following Examples 1 and 2, and Comparative Examples 1 to 7. However, the present invention is not limited to the following Examples.
[0168] Example 1 200 g of tantalum hydroxide and 92 g of 25 mass% ammonia water were mixed and stirred for 10 minutes to obtain a first mixed liquid. Then, 220 g of 35 mass% hydrogen peroxide water was further added to the first mixed liquid and stirred for 10 minutes to obtain a second mixed liquid. Then, 79 g of citric acid was added to the second mixed liquid and stirred for 10 minutes to obtain a peroxo complex aqueous dispersion according to Example 1 containing tantalum, which is a metal carbide precursor according to Example 1.
[0169] The obtained peroxo complex aqueous dispersion according to Example 1 was a transparent solution without precipitation immediately after its production, and was also a transparent solution without precipitation 7 days after its production. The peroxo complex aqueous dispersion according to Example 1 after 7 days of its production had a Ta2O5 equivalent concentration of 175 g / L. Furthermore, the average particle size of the peroxo complex aqueous dispersion according to Example 1 after 7 days of its production was 625.2 nm as measured by a dynamic light scattering method.
[0170] Then, from the peroxo complex aqueous dispersion of Example 1, a powder-shaped metal carbide and a film-shaped metal carbide were produced.
[0171] First, the peroxo complex aqueous dispersion according to Example 1 was placed in a static furnace and dried by heating at a heating temperature of 110° C. for 12 hours, thereby obtaining a peroxo complex powder containing tantalum. The peroxo complex powder containing tantalum was then filled into a carbon crucible, which was then placed in a high-temperature vacuum furnace and fired in the atmosphere at a firing temperature of 1500° C. for 1 hour, thereby obtaining tantalum carbide. The obtained tantalum carbide was then crushed using a ball mill or the like, thereby obtaining a tantalum carbide powder, which is a powder-shaped metal carbide according to Example 1. The tantalum carbide powder according to Example 1 was confirmed to be tantalum carbide (TaC, ICDD card No. 00-019-1292), since a peak was observed in the range of 2θ=33° to 90° from the results of the XRD measurement obtained according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions.
[0172] Next, the peroxo complex aqueous dispersion according to Example 1 was applied onto a carbon black substrate, and the carbon black substrate coated with the peroxo complex aqueous dispersion according to Example 1 was placed in a stationary furnace and dried at a heating temperature of 110° C. for 10 minutes. The dried carbon black substrate coated with the peroxo complex aqueous dispersion according to Example 1 was then placed in a high-temperature vacuum furnace and baked in the atmosphere at a baking temperature of 1600° C. for 60 minutes to obtain a tantalum carbide film, which is a metal carbide film having a film shape according to Example 1. The tantalum carbide film according to Example 1 was confirmed to be a single phase tantalum carbide (TaC, ICDD card No. 00-019-1292) since a peak was observed within the range of 2θ=33 to 90° from the results of XRD measurement obtained according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions.
[0173] Example 2 100 g of niobium hydroxide, 153 g of 25 mass% ammonia water, and 365 g of 35 mass% hydrogen peroxide water were mixed and stirred for 10 minutes to obtain a mixed liquid. Then, 87.6 g of citric acid was added to the mixed liquid and stirred for 10 minutes to obtain a peroxo complex dispersion containing niobium, which is a metal carbide precursor according to Example 2.
[0174] The obtained peroxo complex dispersion according to Example 2 was a transparent solution without precipitation immediately after its production, and was also a transparent solution without precipitation 7 days after its production. The Nb2O5 equivalent concentration of the peroxo complex dispersion according to Example 2 7 days after its production was 133 g / L. Furthermore, the average particle size of the peroxo complex dispersion according to Example 2 7 days after its production was 540 nm as measured by a dynamic light scattering method.
[0175] Then, from the peroxo complex aqueous dispersion of Example 2, a powder-shaped metal carbide and a film-shaped metal carbide were produced.
[0176] First, the peroxo complex dispersion according to Example 2 was placed in a stationary furnace and dried by heating at a heating temperature of 110° C. for 12 hours, thereby obtaining a peroxo complex powder containing niobium. The peroxo complex powder containing niobium was then filled into a carbon crucible, which was then placed in a high-temperature vacuum furnace and fired at a firing temperature of 1500° C. for 1 hour in the atmosphere, thereby obtaining niobium carbide. The obtained niobium carbide was then crushed using a ball mill or the like, thereby obtaining niobium carbide powder, which is a metal carbide according to Example 2. The niobium carbide powder according to Example 2 was confirmed to be niobium carbide (TaNb, PDF card No. 01-076-7071), since a peak was observed in the range of 2θ=33° to 90° from the results of the XRD measurement obtained according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions.
[0177] Next, the peroxo complex aqueous dispersion according to Example 2 was applied onto a carbon black substrate, and the carbon black substrate coated with the peroxo complex aqueous dispersion according to Example 2 was placed in a stationary furnace and dried at a heating temperature of 110° C. for 10 minutes. The carbon black substrate coated with the dried peroxo complex aqueous dispersion according to Example 1 was then placed in a high-temperature vacuum furnace and baked in the atmosphere at a baking temperature of 1600° C. for 60 minutes to obtain a niobium carbide film, which is a metal carbide film in the form of a film according to Example 2. The niobium carbide film according to Example 2 was confirmed to be a single phase niobium carbide (TaNb, PDF card No. 01-076-7071) because a peak was observed within the range of 2θ=33° to 90° from the results of XRD measurement obtained according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions.
[0178] Comparative Example 1 120 kg of tantalum oxide and 22 kg of carbon black were weighed out on a platform balance and mixed in a vertical mixer for 5 minutes to obtain a mixed powder.
[0179] This mixed powder was filled into a carbon container (2 kg / bottle), fed into a resistance heating hydrogen furnace at a rate of two bottles per three hours, and fired at a temperature of 1,700°C for 14 hours to perform primary carbonization, obtaining a primary carbide.
[0180] This primary carbide was filled into a carbon crucible (100 kg / piece), which was then placed in a high-frequency induction heating vacuum furnace and fired at 1,800°C for 5 hours to obtain a secondary carbide.
[0181] The secondary carbide was cooled to room temperature in the high-frequency induction heating vacuum furnace, removed from the carbon crucible, and coarsely crushed into lumps with a diameter of 2 cm or less using a jaw crusher.
[0182] After the coarse crushing, crushing was carried out for 20 hours using a ball mill filled with iron balls of 20 to 50 mmφ, and the coarsely crushed secondary carbide was finely crushed.
[0183] The finely pulverized secondary carbide was then classified using a vibrating sieve, and the undersize particles (fine particle side) were collected to obtain powdered tantalum carbide, which was the metal carbide according to Comparative Example 1.
[0184] Comparative Example 2 In Comparative Example 2, the coarsely crushed secondary carbide was blown through a wind speed of 2.5 m 3 A similar production method to that of Comparative Example 1 was carried out, except that the powdered tantalum carbide of Comparative Example 2 was obtained by finely pulverizing the powdered tantalum carbide using a jet mill, which is an air flow pulverizer, set at a sample feed rate of 10 kg / hr and a sample supply rate of 10 kg / hr.
[0185] Comparative Example 3 In Comparative Example 3, the same manufacturing method as in Comparative Example 1 was carried out except that tantalum oxide was changed to niobium oxide and the amount of carbon black added was changed to 13 kg, thereby obtaining powdered niobium carbide, which is the metal carbide according to Comparative Example 3.
[0186] Comparative Example 4 50 g of tantalum pentachloride was dissolved in a small amount of methanol, water was added, and then 25 mass% ammonia water was added to obtain a precipitate of tantalum acid hydrate Ta2O5·nH2O. The precipitate was washed with water to remove chloride ions, and then 12.57 g of citric acid and 46 g of 25 mass% ammonia water were added and mixed, after which 109 g of 35 mass% hydrogen peroxide water was added and stirred for 10 minutes to obtain a peroxo complex dispersion containing tantalum, which is a metal carbide precursor according to Comparative Example 4.
[0187] The obtained peroxo complex dispersion according to Comparative Example 4 was a transparent solution with a white precipitate immediately after production, and was also a transparent solution with a white precipitate 7 days after production. The peroxo complex dispersion according to Comparative Example 4 7 days after production was centrifuged to separate the white precipitate, and the Ta2O5 equivalent concentration of the dispersion was 39 g / L. Furthermore, the peroxo complex dispersion according to Comparative Example 4 7 days after production contained white precipitate, making it difficult to measure the average particle size by dynamic light scattering.
[0188] The peroxo complex dispersion according to Comparative Example 4 was placed in a stationary furnace and heated and dried at a heating temperature of 110° C. for 12 hours in the same manner as in Example 1 to obtain a dried powder. The obtained dried powder was filled into a carbon crucible, which was then placed in a high-temperature vacuum furnace and fired in the atmosphere at a firing temperature of 1500° C. for 1 hour to obtain a fired powder. The obtained fired powder was confirmed by XRD measurement performed according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions, and it was confirmed that no peak was observed within the range of 2θ=33° to 90°, and that the carbonization reaction had not progressed.
[0189] Comparative Example 5 In Comparative Example 5, a peroxo complex dispersion according to Comparative Example 5 was obtained by carrying out the same production method as in Comparative Example 4, except that the citric acid in Comparative Example 4 was changed to 37.4 g of lactic acid.
[0190] The obtained peroxo complex dispersion liquid according to Comparative Example 5 was a transparent solution with a white precipitate immediately after its production, and was also a transparent solution with a white precipitate 7 days after its production. Moreover, the peroxo complex dispersion liquid according to Comparative Example 5 7 days after its production was centrifuged to separate the white precipitate, and the Ta2O5 equivalent concentration of the dispersion liquid was 2 g / L. Furthermore, the peroxo complex dispersion liquid according to Comparative Example 5 7 days after its production contained white precipitate, making it difficult to measure the average particle size by dynamic light scattering.
[0191] The peroxo complex dispersion according to Comparative Example 5 was placed in a stationary furnace and heated and dried at a heating temperature of 110° C. for 12 hours in the same manner as in Example 1 to obtain a dried powder. The obtained dried powder was filled into a carbon crucible, which was then placed in a high-temperature vacuum furnace and fired in the atmosphere at a firing temperature of 1500° C. for 1 hour to obtain a fired powder. The obtained fired powder was confirmed by XRD measurement performed according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions, and it was confirmed that no peak was observed within the range of 2θ=33° to 90°, and that the carbonization reaction had not progressed.
[0192] Comparative Example 6 In Comparative Example 6, a peroxo complex dispersion according to Comparative Example 6 was obtained by carrying out the same production method as in Comparative Example 4, except that the citric acid in Comparative Example 4 was changed to 92.3 g of tartaric acid.
[0193] The obtained peroxo complex dispersion according to Comparative Example 6 was a transparent solution with a white precipitate immediately after production, and was also a transparent solution with a white precipitate 7 days after production. Moreover, the peroxo complex dispersion according to Comparative Example 6 7 days after production was centrifuged to separate the white precipitate, and the Ta2O5 equivalent concentration of the dispersion was <1 g / L. Furthermore, the peroxo complex dispersion according to Comparative Example 6 7 days after production contained white precipitate, making it difficult to measure the average particle size by dynamic light scattering.
[0194] The peroxo complex dispersion according to Comparative Example 6 was placed in a stationary furnace and heated and dried at a heating temperature of 110° C. for 12 hours in the same manner as in Example 1 to obtain a dried powder. The obtained dried powder was filled into a carbon crucible, which was then placed in a high-temperature vacuum furnace and fired in the atmosphere at a firing temperature of 1500° C. for 1 hour to obtain a fired powder. The obtained fired powder was confirmed by XRD measurement performed according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions, and it was confirmed that no peak was observed within the range of 2θ=33° to 90°, and that the carbonization reaction had not progressed.
[0195] Comparative Example 7 In Comparative Example 7, a peroxo complex dispersion according to Comparative Example 7 was obtained by carrying out the same production method as in Comparative Example 4, except that the citric acid in Comparative Example 4 was changed to 120.2 g of EDTA (ethylenediaminetetraacetic acid).
[0196] The obtained peroxo complex dispersion according to Comparative Example 7 was a transparent solution with a white precipitate immediately after production, and was also a transparent solution with a white precipitate 7 days after production. Moreover, the peroxo complex dispersion according to Comparative Example 7 after 7 days of production, from which the white precipitate was separated using a centrifuge, had a Ta2O5 equivalent concentration of <1 g / L. Furthermore, the peroxo complex dispersion according to Comparative Example 7 after 7 days of production contained white precipitate, making it difficult to measure the average particle size by dynamic light scattering.
[0197] The peroxo complex dispersion according to Comparative Example 7 was placed in a stationary furnace and heated and dried at a heating temperature of 110° C. for 12 hours in the same manner as in Example 1 to obtain a dried powder. The obtained dried powder was filled into a carbon crucible, which was then placed in a high-temperature vacuum furnace and fired in the atmosphere at a firing temperature of 1500° C. for 1 hour to obtain a fired powder. The obtained fired powder was confirmed by XRD measurement performed according to the above-mentioned X-ray diffraction measurement conditions and X-ray diffraction analysis conditions, and it was confirmed that no peak was observed within the range of 2θ=33° to 90°, and that the carbonization reaction had not progressed.
[0198] Next, the metal carbide intermediate dispersion liquid according to the embodiment of the present invention will be further described with reference to the following Examples 3 to 10 and Comparative Examples 8 to 10. However, the present invention is not limited to the following Examples.
[0199] Example 3 A first mixed liquid was obtained by stirring and mixing 200 g of tantalum hydroxide and 92 g of 25 mass % ammonia water for 10 minutes. Then, 220 g of 35 mass % hydrogen peroxide water was further added to the first mixed liquid and stirred for 10 minutes to obtain a second mixed liquid. Then, 79 g of citric acid was added to the second mixed liquid and stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 3. Note that the metal carbide intermediate dispersion liquid according to Example 3 is the same dispersion liquid as the peroxo complex aqueous dispersion liquid according to Example 1 containing tantalum, which is the metal carbide precursor according to Example 1.
[0200] The obtained metal carbide intermediate dispersion liquid according to Example 3 had a Ta content of 0.050 mol (Ta content: 18,800 mass%). The hydrogen peroxide content was 0.009 mol (0.3 mass%), and the ammonia content was 0.2 mol (3.6 mass%). The organic acid (citric acid) content was 0.07 mol (14 mass%). The remainder was water.
[0201] Example 4 200 g of niobium hydroxide, 100 g of 25 mass % ammonia water, and 235 g of 35 mass % hydrogen peroxide water were mixed and stirred for 10 minutes to obtain a mixed liquid. Then, 75 g of citric acid was added to the mixed liquid and stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 4.
[0202] The metal carbide intermediate dispersion liquid according to Example 4 thus obtained had a Nb content of 0.020 mol (3.495% by mass in terms of Nb). The hydrogen peroxide content was 0.009 mol (0.3% by mass), and the ammonia content was 0.2 mol (3.6% by mass). The organic acid (citric acid) content was 0.07 mol (14% by mass). The remainder was water.
[0203] Example 5 In Example 5, 79 g of citric acid and 5 g of lactic acid were added to the second mixed liquid obtained by the same production method as in Example 3, and the mixture was stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 5.
[0204] The obtained metal carbide intermediate dispersion liquid according to Example 5 had a Ta-equivalent content of 0.010 mol (Ta-equivalent content of 4.095% by mass). The hydrogen peroxide content was 0.009 mol (0.3% by mass), and the ammonia content was 0.2 mol (3.6% by mass). The total organic acid (citric acid, lactic acid) content was 0.08 mol (15% by mass), with the breakdown of the total content being 0.07 mol (14% by mass) of citric acid and 0.010 mol (1% by mass) of lactic acid. The remainder was water.
[0205] Example 6 In Example 6, 58 g of tartaric acid was added to the second mixed liquid obtained by the same production method as in Example 3, and the mixture was stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 6.
[0206] The obtained metal carbide intermediate dispersion liquid according to Example 6 had a Ta content of 0.010 mol (Ta content: 4.095% by mass). The hydrogen peroxide content was 0.009 mol (0.3% by mass), and the ammonia content was 0.2 mol (3.6% by mass). The organic acid (tartaric acid) content was 0.09 mol (14% by mass). The remainder was water.
[0207] Example 7 200 g of niobium hydroxide, 100 g of 25 mass% ammonia water, and 235 g of 35 mass% hydrogen peroxide water were mixed and stirred for 10 minutes to obtain a mixed liquid. Then, 75 g of citric acid and 5 g of lactic acid were added to the mixed liquid and stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 7.
[0208] The Nb content in the obtained metal carbide intermediate dispersion liquid according to Example 7 was 0.015 mol (Nb content: 3.495% by mass). The hydrogen peroxide content was 0.009 mol (0.3% by mass), and the ammonia content was 0.2 mol (3.6% by mass). The total organic acid (citric acid, lactic acid) content was 0.08 mol (15% by mass), with the breakdown of the total content being 0.07 mol (14% by mass) of citric acid and 0.010 mol (1% by mass) of lactic acid. The remainder was water.
[0209] Example 8 In Example 8, 75 g of citric acid and 5 g of tartaric acid were added to a mixed liquid obtained by the same production method as in Example 7, and the mixture was stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 8.
[0210] The Nb content in the obtained metal carbide intermediate dispersion liquid according to Example 8 was 0.015 mol (Nb content: 3.495% by mass). The hydrogen peroxide content was 0.009 mol (0.3% by mass), and the ammonia content was 0.2 mol (3.6% by mass). The total organic acid (citric acid, tartaric acid) content was 0.076 mol (15% by mass), with the breakdown of the total content being 0.07 mol (14% by mass) of citric acid and 0.06 mol (1% by mass) of tartaric acid. The remainder was water.
[0211] Example 9 A first mixed solution was obtained by stirring and mixing 100 g of tantalum hydroxide, 100 g of niobium hydroxide, and 100 g of 25 mass% ammonia water for 10 minutes. Then, 235 g of 35 mass% hydrogen peroxide water was further added to the first mixed solution and stirred for 10 minutes to obtain a second mixed solution. Then, 79 g of citric acid was added to the second mixed solution and stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 9.
[0212] The total content in terms of Nb and Ta in the obtained metal carbide intermediate dispersion liquid according to Example 9 was 0.025 mol (the total content in terms of Nb and Ta was 7.590% by mass), and the breakdown of the total content was that the content in terms of Nb was 0.015 mol (the content in terms of Nb was 3.495% by mass), and the content in terms of Ta was 0.010 mol (the content in terms of Ta was 4.095% by mass). The content of hydrogen peroxide was 0.009 mol (0.3% by mass), and the content of ammonia was 0.2 mol (3.6% by mass). The content of organic acid (citric acid) was 0.07 mol (14% by mass). The remainder was water.
[0213] Example 10 In Example 10, 79 g of citric acid, 5 g of tartaric acid, and 5 g of lactic acid were added to a second mixed liquid obtained by the same manufacturing method as in Example 9, and the mixture was stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Example 10.
[0214] The total content in terms of Nb and Ta in the obtained metal carbide intermediate dispersion liquid according to Example 10 was 0.025 mol (the total content in terms of Nb and Ta was 7.590% by mass), and the breakdown of the total content was 0.015 mol (3.495% by mass) in terms of Nb and 0.010 mol (4.05% by mass) in terms of Ta. The hydrogen peroxide content was 0.009 mol (0.3% by mass), and the ammonia content was 0.2 mol (3.6% by mass). The total content of organic acids (citric acid, lactic acid, tartaric acid) was 0.086 mol (16% by mass), and the breakdown of the total content was 0.07 mol (14% by mass) in terms of citric acid, 0.010 mol (1% by mass) in terms of lactic acid, and 0.06 mol (1% by mass) in terms of tartaric acid. The balance was water.
[0215] Comparative Example 8 50 g of tantalum pentachloride was dissolved in a small amount of methanol, water was added, and 25 mass% aqueous ammonia was further added to obtain a precipitate of tantalic acid hydrate Ta2O5·nH2O. The precipitate was washed with water to remove chloride ions, and then 12.57 g of citric acid and 46 g of 25 mass% aqueous ammonia were added and mixed, after which 109 g of 35 mass% aqueous hydrogen peroxide was added and stirred for 10 minutes to obtain a metal carbide intermediate dispersion liquid according to Comparative Example 8. Note that the metal carbide intermediate dispersion liquid according to Comparative Example 8 is the same dispersion liquid as the peroxo complex dispersion liquid according to Comparative Example 4.
[0216] The obtained metal carbide intermediate dispersion liquid according to Comparative Example 8 had a Ta content of 0.009 mol (Ta content: 3.276% by mass). The hydrogen peroxide content was 0.009 mol (0.3% by mass). The organic acid (citric acid) content was 0.07 mol (14% by mass). The remainder was water.
[0217] Comparative Example 9 In Comparative Example 9, a metal carbide intermediate dispersion liquid according to Comparative Example 9 was obtained by carrying out the same production method as in Comparative Example 8, except that the citric acid in Comparative Example 8 was changed to 37.4 g of lactic acid. The metal carbide intermediate dispersion liquid according to Comparative Example 9 is the same dispersion liquid as the peroxo complex dispersion liquid according to Comparative Example 5.
[0218] The metal carbide intermediate dispersion liquid obtained according to Comparative Example 9 had a Ta content of 0.009 mol (Ta content: 0.164% by mass). The hydrogen peroxide content was 0.009 mol (0.3% by mass). The organic acid (lactic acid) content was 0.2 mol (15% by mass). The remainder was water.
[0219] Comparative Example 10 In Comparative Example 10, the same production method as in Comparative Example 8 was carried out except that the citric acid in Comparative Example 8 was changed to 92.3 g of tartaric acid, thereby obtaining a metal carbide intermediate dispersion liquid according to Comparative Example 10. The metal carbide intermediate dispersion liquid according to Comparative Example 10 is the same dispersion liquid as the peroxo complex dispersion liquid according to Comparative Example 6.
[0220] The obtained metal carbide intermediate dispersion liquid according to Comparative Example 10 had a Ta-equivalent content of 0.001 mol (Ta-equivalent content of 0.082% by mass). The hydrogen peroxide content was 0.009 mol (0.3% by mass). The organic acid (tartaric acid) content was 0.1 mol (15% by mass). The remainder was water.
[0221] The following physical properties were measured for the metal carbides according to Examples 1 and 2 and Comparative Examples 1 to 3. The measured physical properties and the methods for measuring the physical properties are shown below, and the measurement results are shown in Table 1. Note that, since the sintered powders according to Comparative Examples 4 to 7 were not carbides according to the results of XRD measurement, the following physical properties were not measured.
[0222] <Elemental analysis> If necessary, the samples were appropriately diluted with hydrofluoric acid and nitric acid, and the Ta mass fraction in Ta equivalent and the Nb mass fraction in Nb equivalent were measured by ICP emission spectrometry (Agilent Technologies: AG-5110).
[0223] <Specific surface area> For each of the powdered metal carbide samples according to Examples 1 and 2 and Comparative Examples 1 to 3, the specific surface area was measured by the BET method in accordance with JIS Z8830 using a fully automatic specific surface area measuring device (Macsorb HM-1230 type).
[0224] <Primary particle size> The specific surface area and carbide density (for example, the density of tantalum carbide is 13.9 [g / cm 3 ]) of each sample of powdered metal carbide according to Examples 1 and 2 and Comparative Examples 1 to 3 are shown in Table 1. 3 ] and the density of niobium carbide is 8.57 [g / cm 3 ] was substituted into the above-mentioned formula (1) to calculate the primary particle size.
[0225] <Circularity> For each sample of powdered metal carbide according to Examples 1 and 2 and Comparative Examples 1 to 3, a scanning electron microscope (SEM) (Hitachi High-Technologies Corporation: S-4800) was used to measure SEM images of the primary particles at a magnification of 10,000 times or more and 100,000 times or less at which the primary particles can be measured. Furthermore, the "long axis" and "short axis" of 20 randomly selected particles were measured using ImageJ, an image analysis software. From the measured "long axis" and "short axis", the circularity was calculated, and the arithmetic mean value of the circularity of multiple particles was taken as the "circularity".
[0226] <Chlorine content measurement> Appropriate amounts of powdered metal carbide samples according to Examples 1 and 2 and Comparative Examples 1 to 3 were collected on ceramic boards, and the samples were heated under argon (Ar) atmosphere at 1000°C for 10 minutes using a combustion ion chromatograph (Nitto Seiko Analytech Co., Ltd.: AQF-2100H) to measure the amount of chlorine generated, thereby determining the chlorine content in each metal carbide powder.
[0227] <Nitrogen content measurement> Appropriate amounts of powdered metal carbide samples according to Examples 1 and 2 and Comparative Examples 1 to 3 were sealed in Ni capsules, and the nitrogen content in each metal carbide powder was determined by a thermal conductivity method using an oxygen / nitrogen analyzer (ON836 manufactured by LECO).
[0228] <Fluidity test 1> 10 g of powder samples of powdered metal carbides according to Examples 1 and 2 and Comparative Examples 1 to 3 were placed in a Tsutsui Rikagakuki Kikai ABD powder property measuring instrument equipped with a filter having a pore size of 850 μm, the filter was vibrated for 1 minute, and the powder sample that passed through the filter was collected. The amount of the powder sample collected was then measured, and the recovery rate was calculated from the formula: Recovery rate = Recovery amount (g) / 10 g x 100. The feed adjustment dial for adjusting the vibration of the filter was set to "8".
[0229] <Fluidity test 2> The pore size of the filter set in the ABD powder property measuring device manufactured by Tsutsui Rikagaku Kikai Co., Ltd. was changed to 1000 μm, measurements were performed in the same manner as in fluidity test 1, and the recovery rate was calculated.
[0230] <Mixed Evaluation> Mixed samples (total 10 g) of powdered metal carbide and tungsten carbide (manufactured by Nippon Shinkinzoku Co., Ltd., particle size 0.8 μm) according to Examples 1 and 2 and Comparative Examples 1 to 3 were weighed so that the molar ratio of the two was 1:1, and were placed in a 100 ml wide-mouthed PP bottle and stirred and mixed for 1 minute using a paint shaker (frequency: 50 Hz). Then, five samples of the mixed samples stirred and mixed were taken using a medicine spoon, and the Ta or Nb mass fraction of each sample was analyzed. Samples in which the difference between the maximum and minimum values of the Ta or Nb analysis values of the five points after stirring and mixing for 1 minute was 0.5 mass% or less were evaluated as having excellent mixability and were evaluated as "○", and samples in which the difference between the maximum and minimum values of the Ta or Nb analysis values of the five points after stirring and mixing for 1 minute was more than 0.5 mass% were evaluated as having poor mixability and were evaluated as "×".
[0231] Furthermore, the following physical properties were measured for the metal carbide intermediate dispersions according to Examples 3 to 10 and Comparative Examples 8 to 10. The measured physical properties and the methods for measuring the physical properties are shown below, and the measurement results are shown in Figs. 1 and 2.
[0232] <Particle size distribution measurement (dynamic light scattering method)> The particle size distribution was evaluated by a dynamic light scattering method according to JIS Z 8828:2019 using a zeta potential, particle size, and molecular weight measurement system (manufactured by Otsuka Electronics Co., Ltd.: ELSZ-2000). In addition, immediately before the measurement, in order to remove dust and the like in the metal carbide intermediate dispersion liquid according to Examples 3 to 10 and Comparative Examples 8 to 10, which are the measurement targets, the dispersion liquid was filtered through a filter with a pore size of 1 μm. Furthermore, D50 indicates the particle diameter that reaches 50% in terms of volume fraction. If the measured particle diameter (D50) is 1 nm or more and 500 nm or less, it is evaluated as "〇〇 (VERY GOOD)", if the particle diameter (D50) is more than 500 nm and 1000 nm or less, it is evaluated as "〇 (GOOD)", and if the particle diameter (D50) is more than 1000 nm, it is evaluated as "× (BAD)". "Initial" in Fig. 2 refers to the metal carbide intermediate dispersion liquids according to Examples 3 to 10 and Comparative Examples 8 to 10 immediately after they were produced. Also, "2 weeks later" or "3 weeks later" in Fig. 2 refers to the metal carbide intermediate dispersion liquids according to Examples 3 to 10 and Comparative Examples 8 to 10 that were allowed to stand for 2 weeks or 3 weeks from the day of production in an incubator set at room temperature of 25°C. Note that since the metal carbide intermediate dispersion liquids according to Comparative Examples 8 to 10 were suspension solutions, the particle diameters (D50) could not be measured.
[0233] <Light transmittance measurement> 3 ml of the metal carbide intermediate dispersion liquid according to Examples 3 to 10 and Comparative Examples 8 to 10 was placed in a glass cell, and the light transmittance in the wavelength region of 350 nm to 750 nm of the metal carbide intermediate dispersion liquid according to Examples 3 to 10 and Comparative Examples 8 to 10 (specifically, the light transmittance at wavelengths of 350 nm, 450 nm, 550 nm, 650 nm, and 750 nm) was measured using a spectrophotometer according to the above-mentioned light transmittance measurement conditions. If the measured light transmittance was 85% or more and 100%, it was evaluated as "〇〇 (VERY GOOD)", if the light transmittance was 70% or more and less than 85%, it was evaluated as "〇 (GOOD)", and if the light transmittance was less than 70%, it was evaluated as "× (BAD)". If the light transmittance was more than 100%, it was considered to be 100%. "Initial" in Fig. 2 refers to the metal carbide intermediate dispersion liquids according to Examples 3 to 10 and Comparative Examples 8 to 10 immediately after they were produced. Also, "2 weeks later" or "3 weeks later" in Fig. 2 refers to the metal carbide intermediate dispersion liquids according to Examples 3 to 10 and Comparative Examples 8 to 10 that were allowed to stand for 2 weeks or 3 weeks from the day of production in an incubator set at room temperature of 25°C. Note that since the metal carbide intermediate dispersion liquids according to Comparative Examples 8 to 10 were suspension solutions, the particle diameters (D50) could not be measured.
[0234] <pH measurement> The metal carbide intermediate dispersion liquids according to Examples 3 to 10 and Comparative Examples 8 to 10 were measured for pH using an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) after confirming that the liquid temperature was stabilized at 25°C. "Initial" in Fig. 2 refers to the metal carbide intermediate dispersion liquids according to Examples 3 to 10 and Comparative Examples 8 to 10 immediately after production. "After 2 weeks" or "After 3 weeks" in Fig. 2 refers to the metal carbide intermediate dispersion liquids according to Examples 3 to 10 and Comparative Examples 8 to 10 left to stand for 2 weeks or 3 weeks from the day of production in an incubator set at room temperature of 25°C.
[0235] [Table 1]
[0236] As shown in Table 1, the metal carbides according to Examples 1 and 2 have a specific surface area of 1 m2 by the BET method. 2 / g or more and the circularity was 0.78 or more, which demonstrated that the particles had high fluidity despite being extremely fine particles.
[0237] The metal carbides according to Examples 1 and 2 had a primary particle size of 0.7 μm or less as measured by the BET method and a circularity of 0.78 or more, and therefore had high fluidity despite being extremely fine particles.
[0238] The metal carbides according to Examples 1 and 2 do not contain hydrogen peroxide because the chlorine content in the metal carbide powder is 25 ppm or less. For example, when the metal carbides according to Examples 1 and 2 are applied to the surface of a crucible to form a film, no foaming occurs and it is easy to apply the metal carbides evenly.
[0239] The metal carbides according to Examples 1 and 2 have a nitrogen content of 1000 ppm or less in the metal carbide powder, and therefore do not contain ammonia components, which is preferable in terms of safety and workability.
[0240] 1 and 2, the metal carbide intermediate dispersions according to Examples 3 to 10 contained a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid, and when the particle size (D50) of the particles in the metal carbide intermediate dispersions was 1000 nm or less as measured by particle size distribution measurement using a dynamic light scattering method, the dispersions had high dispersibility and did not produce precipitates even after a long period of time. Furthermore, the metal carbide intermediate dispersions according to Examples 3 to 10 contained a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid, and the maximum light transmittance of the metal carbide intermediate dispersions in the wavelength range of 350 nm to 750 nm was 70% or more, indicating that the dispersions had high dispersibility and excellent uniformity of the components in the dispersions.
[0241] The metal carbide intermediate dispersions according to Examples 3 to 10 had a pH of 3.0 or more and 10.0 or less, and therefore the polyacid ions contained in the dispersions were stable.
[0242] The metal carbide intermediate dispersions of Examples 3 to 10 had excellent stability and dispersibility because the molar ratio of the organic acid to the metal compound: organic acid / (Nb+Ta) shown in FIG. 1 was greater than 0 and 500, the molar ratio of the hydrogen peroxide to the metal compound: hydrogen peroxide / (Nb+Ta) shown in FIG. 1 was greater than 0 and 10, and the molar ratio of the alkaline compound to the metal compound: ammonia / (Nb+Ta) shown in FIG. 1 was greater than 0 and 100.
[0243] The metal carbide intermediate dispersion liquids of Examples 3 to 10 are suitable in that the thickness of the metal carbide film formed is large because the tantalum content in terms of Ta is 0.4 mass% or more, or the niobium content in terms of Nb is 0.35 mass% or more in the metal carbide intermediate dispersion liquid.
[0244] Moreover, by firing the metal carbide intermediate dispersion liquids according to Examples 3 to 10, metal carbide powders having high fluidity despite being extremely fine particles were obtained.
[0245] Furthermore, the metal carbide intermediate dispersion liquids according to Examples 3 to 10 were applied onto a substrate and fired to obtain metal carbide films.
[0246] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]
[0247] The metal carbide according to the present invention is very fine and has high fluidity, and therefore is suitable as an additive to the raw material of the superhardened tool. Specifically, the metal carbide according to the present invention does not require an excessive mixing process with the raw material of the superhardened tool, and does not require long-term heating during sintering, so that it is possible to reduce energy costs. In addition, the occurrence rate of defective products that cannot be formed into homogeneous superhardened tools due to poor mixability with the raw material of the superhardened tool can be suppressed, so that waste can be reduced and the energy cost for waste disposal can also be reduced. These points lead to the achievement of sustainable management and efficient benefits of natural resources, as well as decarbonization (carbon neutrality).
Claims
1. The method comprises the steps of: a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid; A metal carbide intermediate dispersion liquid, characterized in that the particle size (D50) of particles in the metal carbide intermediate dispersion liquid is 1000 nm or less, as determined by particle size distribution measurement using a dynamic light scattering method.
2. 2. The metal carbide intermediate dispersion liquid according to claim 1, wherein the metal carbide intermediate dispersion liquid has a maximum light transmittance of 70% or more in the wavelength region of 350 nm or more and 750 nm or less.
3. The method comprises the steps of: a metal compound, an alkaline compound, hydrogen peroxide, and an organic acid; a particle size (D50) of particles in the metal carbide intermediate dispersion liquid measured by a particle size distribution using a dynamic light scattering method is 1000 nm or less, and the maximum light transmittance of the metal carbide intermediate dispersion liquid at a wavelength of 350 nm or more and 750 nm or less is 70% or more.
4. 4. The metal carbide intermediate dispersion liquid according to claim 1, wherein the metal compound is a metal hydroxide.
5. 4. The metal carbide intermediate dispersion liquid according to claim 1, wherein the organic acid is citric acid, tartaric acid, or lactic acid.
6. 4. The metal carbide intermediate dispersion liquid according to claim 1, wherein the metal hydroxide is tantalum hydroxide and / or niobium hydroxide.
7. 4. The metal carbide intermediate dispersion liquid according to claim 1, characterized in that the pH is 3.0 or more and 10.0 or less.
8. 4. The metal carbide intermediate dispersion liquid according to claim 1, wherein a molar ratio of the organic acid to the metal compound is greater than 0 and greater than 500, a molar ratio of the hydrogen peroxide to the metal compound is greater than 0 and greater than 10, and a molar ratio of the alkaline compound to the metal compound is greater than 0 and greater than 100.
9. 4. The metal carbide intermediate dispersion liquid according to claim 1, wherein a solvent of the metal carbide intermediate dispersion liquid is water.
10. The metal carbide intermediate dispersion liquid according to any one of claims 1 to 3, characterized in that the metal carbide intermediate dispersion liquid has a tantalum content calculated as Ta of 0.4 mass% or more, or a niobium content calculated as Nb of 0.35 mass% or more.
11. A method for producing a metal carbide intermediate according to any one of claims 1 to 3, comprising the steps of: a complexing step of mixing a metal hydroxide with an alkaline compound to produce a first mixed liquid, adding hydrogen peroxide to the first mixed liquid to produce a second mixed liquid, and further adding an organic acid to the second mixed liquid to produce the metal carbide precursor; a dissolving step of dispersing the metal carbide precursor in pure water to produce a metal carbide intermediate; 2. A method for producing a metal carbide intermediate, comprising the steps of:
12. 12. The method for producing a metal carbide intermediate according to claim 11, further comprising a drying step of drying the metal carbide precursor produced in the complexing step.
13. 13. The method for producing a metal carbide intermediate according to claim 12, further comprising a crushing step of crushing the metal carbide precursor dried in the drying step.
14. 12. The method for producing a metal carbide intermediate according to claim 11, wherein the metal hydroxide is tantalum hydroxide or niobium hydroxide.
Citation Information
Patent Citations
Corrosion-resistant vanadium carbide current collector for halogen positive electrode and preparation method thereof
CN112397723A
Niobium carbide and preparation method thereof
CN114538444A
Preparation method of nano tungsten carbide powder
CN114715894A
Superfine magnetic particles of epsilon' iron carbide and its production
JP1990167810A
Organotantalum aqueous solution and method for producing tantalum lactate peroxy compound crystal
JP2006182714A
Cited By
Metal compound dispersion liquid and method for producing same
WO2026211645A1
Metal compound dispersion liquid and method for producing same
WO2026211646A1
